A structure–sequence synergistic learning framework for prioritizing functional peptides from food protein hydrolysates - Chenxu Zhu; Xinyu Guo; Ziteng Feng; Jiaying Li; Sheng Ke; Gaoheng Li; Zhongkai Zhou; Zhanpeng Jin (Food Research International, 2026)

Substituent-regulated spiropyran/polyurethane fibers with rapid photochromic response and high durability - Jing Li; Ke Liu; Ying Feng; Huiyi Zong; Jinghan Zeng; Xiaohong Liao; Ming Yang; Zhen Wang; Zhen Chen; Changhai Yi; Jin Qian; Kai Wang; et al. (Chemical Engineering Journal, 2026)

Forestation enhances soil organic carbon sequestration with divergent coupling mechanisms along aridity gradients - Nan Huang; Jie Yu Wang; Yuan Chen; Wen Ke Qin; Jia Xie Huang; Chang Ming Zhao; Jin Hua Li (Soil Biology and Biochemistry, 2026)

Kinetic modeling of sorption-enhanced methane steam reforming in a PdAg membrane reactor for sustainable H2 production - Jiaqi Ruan; Ke Guo; Bin Wang; Xiao Li; Mengzhu Sun; Yilin Li; Mingkai Liu; Yong Hao; Hongguang Jin (Chemical Engineering Journal, 2026)

Biomimetic hierarchical scaffold with Zn2+/Mg2+ dual-ion synergistic release for sequential immunomodulation to enhance bone regeneration - Dali Xu; Xin Liu; Jin Li; Jiaxin Quan; Boyang Zhang; Jiawei Zhang; Bowen Zhang; Sihan Lu; W. David Jamieson; Oliver K. Castell; Christopher P. Thomas; Ke Yang; et al. (Chemical Engineering Journal, 2026)

Deciphering the effects of sulfonamide antibiotics on denitrification from a metagenomic perspective: inhibition of nitrite reduction and succession patterns of functional microorganisms - Qinmao Zhou; Yuyang Wang; Hebin Liang; Jin Huang; Jiayu Zhang; Ke Yu; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2026)

Research on multi-cycle recyclable straw heating supply chain design based on intelligent algorithms - Hang Ke; Xin Wu; Jin Li; Jiajia Ye; Mengmeng Sun; Jin Gao; Guangyin Xu; Zhanwu Wang (Journal of Cleaner Production, 2026)

Developing a guide-impact crusher to improve wine grape crushing stability - Ke He; Can Hu; Jin Li; Xiangyu Sun; Yuan Su (Food and Bioproducts Processing, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

A new dipeptide from entomogenous fungus Metapochonia suchlasporia Y9 - Hong-Yan Yang; Jia-Qian Yang; Zhi-Pu Huang; Ke-Tao Zhang; Xin-Yi Chen; Jin-Li Zhao; Yan Wang; Qing Zhao; Xiao-Mei Zhang (Natural Product Research, 2026)

Retraction notice to “Applying thallium isotopic compositions as novel and sensitive proxy for Tl(I)/Tl(III) transformation and source apportionment” [Sci. Total Environ. 913 (2024) 169542] - Juan Liu; Lulu Wang; Jingfen Lin; Wenhuan Yuan; Liangzhong Li; Yung-Kang Peng; Xinni Xiong; Huimin Cao; Xudong Wei; Qi'en Ouyang; Holger Lippold; Jin Wang; et al. (Science of The Total Environment, 2026)

Experimental study on methane explosion suppression by modified coal gangue-KHCO₃ composite powder - Ke Yang; Wenjun Jin; Hong Ji; Jing Liu; Zhixiang Xing; Yong Pan; Xiangyang Li (Process Safety and Environmental Protection, 2026)

Advances in Alzheimer’s disease: mechanistic insights and therapeutic targets - Yu-Juan Jia; Yi-Jun Ge; Bowei Li; Ying Yang; Huaqiu Chen; Jie Liu; Jun-Hong Guo; Jin-Tai Yu; Ke-Qiang Ye; Jian-Zhi Wang; Weihong Song; Yan-Jiang Wang (Science China Life Sciences, 2026)

Continuous Diurnal–Nocturnal Observation of Atmospheric Aerosols: Mechanisms, Challenges, and the Prospects of AI Empowerment - Huizheng Che; Yu Zheng; Lei Li; Ke Gui; Hengheng Zhao; Junli Jin; Xiaochun Zhang; Xiang’ao Xia; Yupeng Wang; Zhiwei Xia; Yucong Miao; Yaqiang Wang; et al. (Journal of Meteorological Research, 2026)

Transcriptomic analysis uncovers mechanisms underlying differential resistance to root rot in different pumpkin (Cucurbita moschata) inbred lines - Haomin Sa; Fengyi Tang; Ruocheng Gao; Xinhui Qiao; Jintao Li; Lele Li; Wanqi Li; Yu Wang; Lifei Yang; Ke Zhang; Guan Pang; Xiaoying Liu; et al. (Physiological and Molecular Plant Pathology, 2026)

Molecular-level fractionation and transformation of dissolved organic matter by schwertmannite during photo-aging: Implications for the carbon cycle in acid mine drainage environments - Qian Yao; Junchun Li; Zhenxing Zhang; Xiaohu Jin; Xiaofei Li; Changdong Ke; Yirong Deng; Guining Lu; Chuling Guo; Zhi Dang; Xiaoyun Yi (Journal of Hazardous Materials, 2026)

Trade-offs and synergies in food and oil security with sustainable agricultural development goals: An emergy-based comparative evaluation of six rice-rape rotation systems in the middle and lower reaches of the Yangtze River - Zhaoqiang Jin; Meilin Chen; Qianqian Chen; Xinyue Xu; Yuanying Luo; Xiangshan Li; Shubin Yan; Sifan Duan; Matthew Tom Harrison; Ke Liu; Shijie Shi; Yifan Li; et al. (Field Crops Research, 2026)

In-situ monitoring reveals the determinants of dissolved methane concentrations within seagrass meadows in a lagoon in northern China - Rui Jin; Xiaoyong Duan; Ping Yin; Xue Li; Bin Chen; Ke Cao; Shenghua Lv; Daolai Zhang; Xingliang He; Xianguo Li; Dahai Zhang (Acta Oceanologica Sinica, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The ZxCNIH4-ZxHKT1;1 module responding to external NaCl orchestrates Na+ partitioning in a xerophyte - Jie Huang; Pei-Qin Li; Tian-Qiong Wang; Wan-Peng Bai; Hu-Jun Li; Jin Ke; Yuan-Zhou Pan; Suo-Min Wang (Plant Science, 2026)

UPLC-PDA-MS guided isolation of lindenane sesquiterpene oligomers with anti-neuroinflammatory activity from two rare Chloranthus species - Jun-Li Xin; Ke-Xin Li; Zhi-Xuan Wang; Xian-Neng Lu; Xue-Jiao Wang; Yi-Cheng Mao; Jin-Feng Hu; Juan Xiong (Phytochemistry, 2026)

Melatonin safeguards embryo and blastoid development against oxybenzone toxicity via a mitochondrial-linked NAD+ and glucose metabolic axis - Yuying Xiong; Haiying Zhu; Han Xie; Yunqi Wu; Ruojin Shi; Xueling Zhang; Lin Zhu; Yiwen Wang; Ke Zhong; Lei Li; Yaming Meng; Minyu Xie; et al. (Environmental Pollution, 2026)

Changes of canopy nitrogen distribution and nitrogen metabolism in hybrid rice under global dimming: A three-year field study - Liying Huang; Fangfang Hou; Wanting Li; Liyan Shang; Shuaijun Dai; Chunhu Wang; Ke Liu; Zhaoqiang Jin; Shijie Shi; Xiaohai Tian; Yunbo Zhang (European Journal of Agronomy, 2026)

Antibiotic resistance genes in drinking water: Absolute abundance, mobility, and hosts across the source-to-tap continuum - Jie Liu; Renxin Zhao; Jin Huang; Uli Klümper; Ke Yu; Jiayu Zhang; Guijuan Zhang; Thomas U. Berendonk; Ryo Honda; Yang Yu; Jian Sun; George Wells; et al. (Chemical Engineering Journal, 2026)

Mechanisms underlying DEHP/MEHP-induced toxicity in multiple sclerosis: An integrated analysis combining network toxicology, bioinformatics, and in vivo experimental validation - Ke An; Wenjun Wang; Xunhao Mao; Zeqiang Jin; Chang Li; Yue Cao; Jing Cao (Chemico-Biological Interactions, 2026)

Verbascoside reverses GABAergic deficits in the prefrontal cortex to alleviate chronic Stress-Induced depression - Jin Pan; Liuxuan Huang; Peng Sun; Haoquan Tian; Wenguang Yang; Xinyu Fang; Feng Li; Ke Ma (Psychopharmacology, 2026)

Comprehensive Analysis of Mixed Reproductive Health Effects of Neonicotinoids: Association with Declining Sperm Concentration and Total Sperm Count in Men - Ruyun Liu; Xun Li; Yilin Xue; Xuanxuan Wang; Cheng Wang; Shulin Yang; Tao Zhang; Dan Hu; Si Liu; Jing Yue; Lei Jin; Ke Gao; et al. (Exposure and Health, 2026)

Crustacean cardioactive peptide activates pupal ecdysial behavior in the 28-spotted larger potato ladybird - Yi-Kuan Wu; Nan Wu; Wei-kang Zheng; Li-ke Ding; Yi-fei Wu; Lin Jin; Guo-Qing Li (Pesticide Biochemistry and Physiology, 2026)

How front-of-pack nutrition labels function to reduce purchases of high-sugar products: evidence from China - Lijun Guan; Zekang Li; Qianyan Wang; Shaosheng Jin; Fuyan Ke (Food Quality and Preference, 2026)

In-situ copolymerization of poly(methyl methacrylate)-based quasi solid electrolyte coupled with a special 3D cage for solid state lithium metal batteries - Sailong Wang; Haoxiang Liu; Yarong Wang; Ke Li; Jie He; Peijun Zhu; Zhixiong Zou; Chao Jin; Guobing Zhou; Ruizhi Yang (Chemical Engineering Journal, 2026)

Application of Magnetic-Seismic Geophysical Prospecting Technology in Identifying the Carboniferous Volcanic Rocks in the Chepaizi, West Margin of Junggar Basin - Guo-hua Jiao; Wei-ping Zhang; Jin-ke Zhou; Fu-gang Sun; Hai-tao Yang; Man Li; Zhu-qiang Li (Applied Geophysics, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Elucidating the molecular mechanism of pancreatic lipase inhibition by small molecules from Auricularia auricula-judae via integrated biophysical approaches - Xia Yin; Hui-Min Li; Jia-Yang Xu; Han Wu; Meng-Yue Dong; Ke-Ran Hao; Jin-Ming Gao (Food Bioscience, 2026)

Decadal straw and biochar amendments in calcareous soils: Contrasting abiotic retention and biotic mineralization processes shape phosphorus availability - Yunxian Zhang; Qin Liu; Zhangliu Du; Zhibo Wang; Yalan Chen; Yang Li; Jie Jin; Ke Sun (Soil and Tillage Research, 2026)

Long-term assessment of natural mineral-based electrochemical systems for concurrent wastewater treatment and nutrient recovery - Yukun Xing; Shuting Chen; Baile Wu; Xiyuan Feng; Ke Hu; Xiaoxiang Zhang; Junyu Zhou; Jingsheng Shi; Yafei He; Peng Li; Zhengyu Jin (Journal of Water Process Engineering, 2026)

Dietary metal(loid)s exposure and their health risks to patients with gastric precancerous lesions and gastric cancer in Anhui Province, Eastern China - Mengran Ke; Qingsong Jiang; Yan Zhu; Bowen Zhang; Daqiang Li; Princess Ofosuhemaa; Guoqing Jin; Yuting Zhu; Wuqi Wang; Meng Zhang; Li Wang; Shaopeng Ding; et al. (Journal of Environmental Sciences, 2026)

Synergistic effects of radicals and NaCl on quality deterioration in salted egg yolks oxidation and quality deterioration - Jing Guo; Ke Tian; Manman Li; Wei Xue; Yongguo Jin (Food Research International, 2026)

Comprehensive evaluation of sustainability of dry direct-seeded, wet direct-seeded, and transplanted rice-wheat rotation systems in the middle and lower reaches of the Yangtze river based on emergy analysis - Zhaoqiang Jin; Beiyou Zhang; Qianqian Chen; Meilin Chen; Sifan Duan; Yuanying Luo; Shubin Yan; Xiangshan Li; Matthew Tom Harrison; Shijie Shi; Ke Liu; Liying Huang; et al. (Field Crops Research, 2026)

Geometric properties and cross-section behaviour of wire arc additively manufactured AA5356 I-section and cruciform-section stub columns - Jin Li; Ke Jiang; Ziyi Wang; Man-Tai Chen; Ou Zhao (Engineering Structures, 2026)

Investigation of the size effect and explosion mechanism of fire-extinguishing microcapsules using a 3D-printed non-planar microfluidic platform - Ming Cao; Xiaoshan Jin; Meirong Yi; Jianfeng Chen; Yichuan Dai; Xiaoxiao Chen; Fangsheng Huang; Zhiqiang Zhu; Shengyun Ji; Ke Li; Xun Cai (Chemical Engineering Journal, 2026)

A net-like colloid with peculiar CO2 sorption behavior formed by aggregation of organic ligand molecules in water - Jin Cai; Wan Chen; Hai Li; Xin Zheng; Han Tang; Ming-Ke Yang; Zi-Xuan Huang; Zi-Ying Zhao; Peng Xiao; Yun-Lei Peng; Xian-Ren Zhang; Long-Long Xie; et al. (Chemical Engineering Journal, 2026)

Construction of electrostatically self-assembled pomelo peel/carbon nanotube aerogel and the modulation of thermal performance in composite phase change material - Jianming Li; Aikun Tang; Yi Jin; Tao Cai; Ke Chen; Shanshan Shao (Biomass and Bioenergy, 2026)

Integrated plant-soil-microbiome responses mediate greenhouse gas emissions in the restoration of a semiarid steppe - Zhen Wang; Xiaojiang Yang; Paul C. Struik; Muhammad Nadeem Ashraf; Carmeron N. Carlyle; Scott X. Chang; Yuanheng Li; Wenbo Zhang; Riliga Wu; Baoming Ji; Ke Jin (Applied Soil Ecology, 2026)

Ecological distribution and functional characterization of polyethylene-degrading enzymes from diverse metagenomes - Ning Wang; Meiling Jin; Zixuan Zhu; Yuxin Wang; Xinyu Li; Jing Xu; Shijunyi Cheng; Yuanying Zhu; Ruiqi Wang; Tong Xu; Furong Yin; Xinyue Li; et al. (Science of The Total Environment, 2026)

Development and application of integrated adsorption–fluidized-bed desorption–RTO process for high-flowrate rubber vulcanization exhaust - Shanshan Guo; Boxian Chen; Yufei Cai; Cui Li; Ling Ma; Zhentao Wang; Yuting Huang; Weibing Wu; Ke Jin; Xingyu Jiang; Weirong Zhao (Chemical Engineering Journal, 2026)

pH-responsive tannic acid-iron nanozymes capable of self-adaptive regulation of oxidative stress for enhancing the treatment of MRSA-infected wound via disrupting PBP2a to restore methicillin sensitivity - Yuze Luo; Ying Wang; Cheng Jin; Ke Yang; Zefeng Wang; Yinbang Zheng; Junqin Li; Chunlei Ou; Li Wang; Dinggeng He (Chemical Engineering Journal, 2026)

Cervical spondylotic myelopathy caused by cervical dystonia: a case report - Shuang Li; Maolin Fu; Yuan Gao; Ke Li; Runnu Jin; Lan Wen (Acta Neurologica Belgica, 2026)

A finite-time adaptive fault-tolerant control method for a fractional-order ship power system - Ying Li; Jin Ke; Tao Xie (Ocean Engineering, 2026)

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Comparative study on organic composts in blueberry: insights into soil physicochemical properties and heavy metal control - Hao Tang; Ying Dai; Lijuan Tang; Juan Guo; Ke Wen; Fangke Yuan; Lin Li; Yuan Jin; Jinlu Li; Min Xiao; Heng Xu (Environmental Geochemistry and Health, 2026)

Chi-miR-146a promotes the propagation of Neospora caninum by targeting the TGF-β1/SMAD2 pathway - Jin-Ming Chen; Jing-Yu Li; Jia-Yi Jin; Xiao-Qi Bao; De-Liang Tao; Xiao-Yun Zhao; Jun-Ke Song; Xin Yang; Ying-Ying Fan; Guang-Hui Zhao (Veterinary Parasitology, 2025)

The coupling of bacterial and fungal diversity under land-use conversion in global grassland regions is limited by perturbation intensity - Tongrui Zhang; Shucheng Li; Tingting Xing; Jiayue Liu; Zhaokai Sun; Zhenyu Yao; Shiming Tang; Ke Jin (Soil and Tillage Research, 2025)

Coupled MICP–MISP biotechnologies for eco-friendly dust control in open-pit coal mines: Strength enhancement and ammonium recycling - Wen Nie; Jin Shi; Ruoxi Li; Wenjin Niu; Qifan Tian; Ke Tong; Zhihui Zhang (Journal of Environmental Chemical Engineering, 2025)

Contrast of composition and sources of PM2.5 and PM10 in Shenzhen, China: Revealing key factors on health risks - Xing Peng; Li He; Ling-Yan He; Jiang-Yao Tan; Ke-Jin Tang; Wen-Jie Yu; Wen-Wei He; Xiao-Feng Huang (Journal of Environmental Management, 2025)

Biodegradation of unpretreated polypropylene microplastic and agricultural polypropylene film by a bacterium isolated from an oil reservoir - Sheng Jin Li; Yun Yang Wan; Zhe Ke Zhong; Ying Jia Zhu; Hong Mei Mu; Sheng Bao Shi (Journal of Environmental Chemical Engineering, 2025)

Floc-granule microbial symbiosis drives DNRA in anammox bacteria via cross-feeding for complete autotrophic nitrogen removal - Yulong Yang; Wen-Bo Nie; Xin Tan; Lili Li; Chenhui Yu; Shibo Fu; Ke-Di Peng; Yi Luo; Xiao Ran; Zhihong Zheng; Jin Xu; Jun Li; et al. (Chemical Engineering Journal, 2025)

Multiband bipolar photoresponse in Cu@CuOx@a-Ga2O3 core-shell heterostructure-based self-powered photoelectrochemical-type photodetector for secure underwater optical communication - Yixin Sun; Yan Tang; Xiuhong Jiang; Aijiang Yan; Jin Zhao; Yuchuan Wang; Jiangshuai Luo; Jili Jiang; Ke Ding; Hong Zhang; Honglin Li; Di Pang; et al. (Chemical Engineering Journal, 2025)

Changes in belowground biomass dominate soil phosphorus availability in grazed grasslands - Shucheng Li; Ke Jin; Shiming Tang; Hongyang Chen; Hong Sun (Agriculture, Ecosystems & Environment, 2025)

PICK1 modulates the proliferation and migration of gastric cancer cells by regulating TLR4 - Kaiqiang Li; Yimin Yang; Yaling Wang; Jing Jin; Qianni Wang; Lina Peng; Aibo Xu; Xuling Luo; Wei Yang; Peng Xu; Bingyu Chen; Ke Hao; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Contarinia maculipennis, a worldwide invasive flower and vegetable pest possessing the particularities of rearrangement and tRNA secondary structures of mitogenome: A potential key to revealing its extensive host radiation - Ning-Bo Ma; Xiu-Fang Dong; Yu Ji; Xin Jin; De-Wei Wei; Yan-Fei Li; Zheng-Hao Yue; Wen-Jun Bu; Ke-Long Jiao (Zoologischer Anzeiger, 2025)

Determination of dynamic shear stress and strain thresholds in frozen coarse-grained materials: experimental and M-K statistical analysis - Shanzhen Li; Shuang Tian; Liang Tang; Xianzhang Ling; Huijun Jin; Wenjian Zhao; Ke Wang; Xiao Han (Transportation Geotechnics, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

One fell swoop strategy to detect and degrade malathion by an ALP-sensitive and Pt-Co-N-C nanozyme-enhanced chemiluminescent 3D μPAD - Yang Chen; Qi Zhang; Ruiqing Ke; Tianyi Ma; Kunlun Huang; Yunbo Luo; Jin-Cheng Li; Nan Cheng (Food Chemistry, 2025)

Synergistic coupling of Pd@PtRh nanozyme with NiMn2O4/In2S3 Z-scheme heterojunction for ultrasensitive photoelectrochemical sensing of malathion - Rui-Jin Shao; Ke Yin; Lei Zhao; Yadong Xue; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2025)

Revisiting the genesis of Bi-Te-Au-S associations: Implications for the ore-forming processes in gold deposits - Gao-Hua Fan; Jian-Wei Li; Zhan-Ke Li; Xue-Feng Yu; Xiao-Dong Deng; Jin-Hao Liu; Hang-Jin Jiang; Hong-Jun Sun; Tian-Ming Zhang (Chemical Geology, 2025)

Various formation pathways of size-resolved secondary organic aerosols at a coastal site in Eastern China - Meng-Xue Tang; Jia-Yuan Wang; Ke-Jin Tang; Wen-Jie Yu; Li He; Xiao-Feng Huang; Ling-Yan He; Hui Zeng; Si-Hua Lu; Min Hu (Atmospheric Environment, 2025)

Deciphering the biomolecular mechanisms of calcite precipitation of multi-metals by the novel metallotolerant strain Priestia aryabhattai PMASS1 - Edidiong Okokon Atakpa; Jin Li; Faqin Dong; Wu Lei; Chen Lei; Zhang Yunyi; Hu Ke; Fidèle Suanon; Frank Sesu; Lei Zhou; Lv Zhenzhen; Huo Tingting; et al. (Journal of Environmental Chemical Engineering, 2025)

Integrated multi-omics dissection unveils transcriptional and miRNA-mediated regulation of amino acid biosynthesis networks during bud-to-bloom transition in Hemerocallis citrina - Xiao-Ke Li; Jin-Long Cui; Xue-Mei Qin (Food Bioscience, 2025)

All-in-one photothermal hydrogel: Graphene@CuS with microchannels for fast evaporation, water purification, and heat reuse - Lin Lin; Jin Yang; Danyi Li; Siyi Xu; Fangzheng Wang; Xiaoshan Zhou; Yongan Ke; Linfan Li; Jihao Li (Chemical Engineering Journal, 2025)

A ratiometric fluorescence probe based on curcumin and supramolecular deep eutectic solvent for in vivo imaging cerebral pH - Wan-Chun Luo; Jin-Tao Zhang; Li-Na Bao; Lin-Jiao Yang; Zi-Ke Yang; Ming Jiang; Xu Yu; Li Xu (Chemical Engineering Journal, 2025)

Organotins as inhibitors targeting human and rat steroid 5α-reductase 1: structure-activity relationship and docking analysis - Shufang Qi; Rong Cui; Wanyu Li; Jin Yang; Ke Zheng; Shaowei Wang; Ren-Shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2025)

Pseudomonas bambusae sp.nov., an Aniline Blue-Decolorizing Bacterium Isolated from Decaying Round Bamboo Culms - Xiao-Long He; Jia-Yan Wang; Jin-Jia Liang; Cheng-Jing Ren; Xin-Yi Guo; Wen-Jie Ke; Min Wu; Hong-Zheng Liu; Min Jin; Fang-Li Sun; Shuai-Bo Han (Current Microbiology, 2025)

Three new aliphatic compounds from the roots of Saposhnikovia divaricata and their antiproliferative activity on HepG2 cells - Yan Liu; Jin-Hong Xue; Yan Sun; Fan-Ying Deng; Si-Yi Wang; Juan Pan; Zhi-Chao Hao; Ke-Zhen Chen; Anam Naseem; Qing-Shan Chen; Li-Li Zhang; Hai-Xue Kuang; et al. (Natural Product Research, 2025)

Upstream moisture sources and circulation patterns controls Asian monsoon hydroclimate over the past 20,000 years - Jian Zhang; Ming-Qiang Liang; Jun-Yun Li; Yao Wu; Yan-Xia Xue; Wen-Jun Sun; Xiang-Zhuo Liu; Jin-Ke Chen; Chao-Jun Chen; Ting-Yong Li (Quaternary Science Reviews, 2025)

Mechanistic insights into plasmon-mediated charge transfer in Pt@BiOBr/g-C3N4 S-scheme heterojunction for solar-driven water treatment - Jin Chen; Ke Li; Jie Yan; Suqing Qin; Yuzhao Ma; Xiaofeng Yang; Yanjun Li (Journal of Water Process Engineering, 2025)

Empowering a coupled hydrological-geotechnical model to simulate long-term vegetation dynamics and their impact on catchment-scale flood and landslide hazards - Guoding Chen; Ke Zhang; Yunping Li; Jin Feng; Thom Bogaard (Journal of Hydrology, 2025)

Phthalocyanine-based nanosensitizers for enhanced sonodynamic therapy activity of hypoxic tumor with dual apoptosis/ferroptosis pathways - Xue-Yan Li; Jin Liu; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang (Journal of Photochemistry and Photobiology B: Biology, 2025)

STANet-TLA: leveraging deep learning and prior knowledge for large-scale soybean breeding plot segmentation and high-yielding variety screening from UAV time-series data - Shaochen Li; Yinmeng Song; Ke Wang; Yiqiang Liu; Junhong Xian; Hongshan Wu; Xintong Zhang; Yanjun Su; Jin Wu; Qinghua Guo; Shan Xu; Dong Jiang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

An approach and mechanistic insights of coating-type binders for 4.6 V-LiCoO2 cathode of lithium-ion battery - Li Deng; Yu-Xi Luo; Zhen Wang; Jin-Xia Lin; Jun-Ke Liu; Kun-Gui Zheng; Gao-Yang Bai; Zu-Wei Yin; Yao Zhou; Jun-Tao Li (Chemical Engineering Journal, 2025)

Identification of an adaptor protein 2σ gene for OsTGW12 to determine grain weight and potentiate quality breeding in rice - Xiaoqiong Li; Huangai Li; Ke Xie; Jinling Han; Kaiqiang Liu; Ying Chen; Jingang Qi; Hongpei Jin; Hanhua Tong; Aihua Sha; Sibin Guo (Theoretical and Applied Genetics, 2025)

A time-domain multi-parameter elastic full waveform inversion with pseudo-Hessian preconditioning - Jian-ping Huang; Zhang Liu; Ke-jie Jin; Kai-lun Ba; Yu-hang Liu; Ling-hang Kong; Chao Cui; Chuang Li (Applied Geophysics, 2025)

A critical need to control thallium contamination in aquatic ecosystem for the age of low carbon - Juan Liu; Wenhuan Yuan; Yu Shi; Yanyi Liu; Pei Li; Wanpeng Chen; Xuan Zeng; Ying Li; Ke Lin; Yinyin Lu; Haiyao Hu; Jin Wang (Journal of Hazardous Materials, 2025)

Research progress of high-strength self-healing polymer materials: Balance between mechanical strength and self-healing efficiency - Zhi-Hui Yan; Hua-Xin Huang; Guo-Quan Ding; Shan-Shan Dong; Ke-Jin Jiang; Yu-Ying Li; Yang Liu; Yan Jiang; Shuang-Fei Wang; Guo-Hua Hu; Jun Du; Shi-Xian Zhang; et al. (Chemical Engineering Journal, 2025)

Post-fire behaviour of wire arc additively manufactured ER70S-6 steel - Jin Li; Ke Jiang; Man-Tai Chen; Ou Zhao; Leroy Gardner (Engineering Structures, 2025)

Nano-Selenium supplementation Improves Meat Quality, Protein Deposition, and Selenoprotein Gene Expression in Channel Catfish (Ictalurus Punctatus) - Zi Meng Li; Xiao Min Jin; Hui Long Qiu; Wen Hao Xu; Cong Hu; Ke Chen; Jia Qiang Huang; Lian Shun Wang (Biological Trace Element Research, 2025)

Enhanced resilience to oxygen exposure and toxicity of chlorinated solvents in immobilized Dehalococcoides mccartyi - Jingjing Wang; Xiuying Li; Huijuan Jin; Yiru Cui; Lisi Jiang; Siqi Huang; Ke Shi; Jun Yan (Journal of Hazardous Materials, 2025)

Thermal sensation prediction model for the elderly in rural areas of cold regions under winter conditions - Wenjing He; Difei Yin; Ke Li; Jin Zhan; Shanshan Wang (Energy and Buildings, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Synergy of bismuth and tungsten in Bi2WO6 for PMS activation to enhance degradation of ammonium dibutyl dithiophosphate in flotation wastewater - Mingwei Shen; Teng Wang; Yawei Wang; Zhiyuan Li; Jiayou Liu; Ke Jin; Hesheng Yu (Journal of Water Process Engineering, 2025)

Electrospun sodium titanate-MXene/carbon nanofibers as binder-free electrode for enhanced hybrid capacitive deionization - Xin Li; Xiang Fu; Youfang Zhang; Qunchao Zhang; Zhaoyang Wei; Ke Wang; Robert K.Y. Li; Dean Shi; Jun Jin (Chemical Engineering Journal, 2025)

Soil microbiome mediates plant community productivity in grass–legume mixtures - Jing Li; Zhuwen Xu; Wenbo Zhang; Xiaojiang Yang; Paul C. Struik; Shenyi Jiang; Zhen Wang; Ke Jin (Plant and Soil, 2025)

Hand in hand catalytic hairpin assembly-based FÖrster resonance energy transfer biosensor for simultaneous detection of multiple MicroRNAs from breast cancer - Noshin Afshan; Tao Cheng; Jiabao Yu; Ke Jiao; Lie Li; Jianwei Jiao; Jin Jiao (Analytica Chimica Acta, 2025)

The global effects of grazing on grassland soil nitrogen retention - Shucheng Li; Kaiwei Li; Tongrui Zhang; Shiming Tang; Zhe Zhang; Hongyang Chen; Ke Jin (Agriculture, Ecosystems & Environment, 2025)

Urinary concentrations of phthalate metabolites and the survival of high-grade serous ovarian cancer with advanced stage - Wen-Rui Zheng; Yi-Zi Li; Jin Xu; Ke-Xin Liu; Fang-Hua Liu; Wei-Yi Xing; Jia-Xin Liu; Lang Wu; Xiao-Ying Li; Dong-Hui Huang; Ting-Ting Gong; Qi-Jun Wu (Environmental Pollution, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Paeoniflorin-mediated downregulation of VEGFA: unveiling the therapeutic mechanism of buyang huanwu decoction in diabetic retinopathy - Wentao Sun; Rui Wang; Ke Gong; Liping Wang; Fengzhi Li; Jin Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Grazing exclusion changes the complexity and stability but not the α-diversity of the microbial community in a desert steppe - Fengqin Yuan; Xuebao Xu; Zhenpeng Liu; Rula Sa; Chongzhi Sun; Jia Liu; Na Li; Yujuan Zhang; Tongrui Zhang; Tingting Xing; Jie Ren; Shiming Tang; et al. (Applied Soil Ecology, 2025)

Organic fertilizations alter the abundance and diversity of soil microbial genes involved in C, N, P mineralization in a coastal poplar plantation - Tingting Ren; Jiahui Liao; Xiaoming Zou; Yuanyuan Li; Juanping Ni; Ke Shi; Long Jin; Manuel Delgado-Baquerizo; Honghua Ruan (Applied Soil Ecology, 2025)

Risk assessment of broflanilide resistance in Panonychus citri (McGregor): Cross-resistance, inheritance and relative fitness - Ke Li; Chunyu Zhang; Yiting Ren; Xunyan Liu; Deng Pan; Wei Dou; Jin-Jun Wang; Guorui Yuan (Pesticide Biochemistry and Physiology, 2025)

Comparative analysis of fecundity related traits and transcriptome in two isofemale lines of the egg parasitoid, Trichogramma dendrolimi (Matsumura) - Hong-Yu Liang; An-Ke Liu; Ning He; Jin-Cheng Zhou; Xiao-Hui Ma; Li-Sheng Zhang; Wu-Nan Che; Hui Dong (Journal of Asia-Pacific Entomology, 2025)

Carbon nanotube-based solid-state mid-infrared electrochromic devices for smart outdoor thermal management - Ke Jiao; Zongtao Zhang; Yifei Liu; Jin Li; Chao Xue; Jing Zhang; Yunxiang Chen; Zhang Chen; Xinghui Hou; Liying Zhang; José V. Anguita; Wei Zhang; et al. (Chemical Engineering Journal, 2025)

Detecting monogenic disorders in utero non-invasively based on fetal nucleated red blood cells highly-purified by multi-functional magnetic nanoparticles - Lin Cheng; Chun Feng; Ke Wu; Zixiang Wang; Wentao Zhu; Ting Geng; Naiqi Li; Jiawei Kang; Jie Duan; Jin Li; Yuqi Shao; Saisai Yang; et al. (Analytica Chimica Acta, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Molecular epidemiology and antimicrobial resistance of Vibrio parahaemolyticus isolates from the Pearl River Delta region, China - Qianru Wang; Qingmei Li; Fangzhu Ouyang; Bixia Ke; Shiqin Jiang; Jiajun Liu; Jin Yan; Baisheng Li; Wei Tan; Dongmei He (International Journal of Food Microbiology, 2025)

Nitrogen vacancy mediated g-C3N4/BiVO4 Z-scheme heterostructure nanostructures for exceptional photocatalytic performance - Xiaoyan Zhong; Yuanli Li; Sili Liu; Qian Liu; Ke Yang; Xinhua Li; Wanchuan Jin; Haifeng Liu; Ruishi Xie (Environmental Research, 2025)

Grazing intensity by sheep affects spatial diversity in botanical composition of Inner Mongolian grassland - Xu Han; Raúl Ochoa-Hueso; Yong Ding; Xiliang Li; Ke Jin; Wim H. van der Putten; Paul C. Struik (Agriculture, Ecosystems & Environment, 2025)

Seven undescribed compounds from dried flower buds of Ochrocarpus longifolius - Shu-Lan Liu; Xue-Ling Huang; Shun-Hua Zhong; Yong-Hui Ma; Feng Wei; Yu-Ye Zhang; Jin Li; Ke-Jian Pang; Ping Zhao; Xin-Zhou Yang (Phytochemistry, 2025)

Structure-Directing role of support on toluene catalytic combustion over Pt/TiO2 catalysts - Jin Yuan; Kun Yang; Jianqiang Shi; Jinxing Mi; Ke Zheng; Jianjun Chen; Junhua Li (Fuel, 2025)

Prospective LCA towards achieving carbon neutrality goals: Framework application and challenges - Ya-Xi Fang; Pei-Ze Wu; Sha Chen; Yu Li; Shu-Fen Cui; Jin-Xing Zhu; Hai-Zhou Cao; Ke-Jun Jiang; Ling Zhong (Environmental Impact Assessment Review, 2025)

Flexible and large-area electrochromic infrared devices with superior modulation functionality - Zongtao Zhang; Yifei Liu; Ke Jiao; Yunxiang Chen; Jing Tong; Jin Li; Miaoran Xu; Chao Xue; José V. Anguita; Jing Zhang; Kai Yang; Wei Zhang; et al. (Chemical Engineering Journal, 2025)

A study on the scaled intelligent supply mode of biomass briquette fuel in China - Hang Ke; Xiaolei Zhu; Mingyue Ding; Guanghui Xu; Baoqian Li; Jin Li; Yufeng Sun; Guangyin Xu; Runkai Zhang (Science of The Total Environment, 2024)

The novel prognostic analysis of AML based on ferroptosis and cuproptosis related genes - Mei Wu; Anan Li; Tingting Zhang; Weirong Ding; Yujing Wei; Caishui Wan; Bo Ke; Hongbo Cheng; Chenghao Jin; Chunfang Kong (Journal of Trace Elements in Medicine and Biology, 2024)

Increased atmospheric thallium threats to populated areas: A mini review - Juan Liu; Yaole Huang; Yanyi Liu; Shunlong Jiang; Qiong Zhang; Pei Li; Ke Lin; Xuan Zeng; Haiyao Hu; Yang Cao; Xinni Xiong; Jin Wang (Journal of Hazardous Materials, 2024)

Efficient ozone decomposition by optimizing defect sites of NiMn-layered double hydroxides under high humidity air - Hongyang Jin; Zhen Li; Xin Min; Lei Zhong; Ke Chen; Songjian Zhao (Journal of Environmental Chemical Engineering, 2024)

Analysis of wheat fungal community succession in traditional storage structures using Illumina MiSeq sequencing technology - Ruihu Wang; Mengmeng Li; Rui Jin; Yuanxiao Liu; Erqi Guan; Sherif Ramzy Mohamed; Ke Bian (International Journal of Food Microbiology, 2024)

Tensile behavior of needle-punched nonwoven geotextiles based on in-situ X-ray computed tomography and numerical simulation - Ke-Yi Li; Xiao-Wu Tang; Min-Liang Fei; Shi-jin Feng; Jia-jie Tang; Qing-Qing Xiang; Heng-yu Wang (Geotextiles and Geomembranes, 2024)

Microbial community succession and changes of volatile compounds in the fermentation process of bamboo shoots - Jinmei Wei; Zongjun Li; Jinyan Kuang; Zikang Yan; Li Wang; Ying Lin; Jin Du; Ke Li; Yuanliang Wang; Li Yang (Food Microbiology, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Embryonic Genome Activation (EGA) Occurred at 1-Cell Stage of Embryonic Development in the Mud Crab, Scylla paramamosain, Revealed by RNA-Seq - Li-Kun Xu; Chun-Yan Ma; Feng-Ying Zhang; Wei Wang; Ming Zhao; Xin Jin; Jin-Ju Yin; Ling-Bo Ma; Wei Chen; Jia-Yuan Xu; Ke-Yi Ma; Zhi-Qiang Liu (Marine Biotechnology, 2024)

Fluid evolution and genesis of the Shipenggou gold deposit in Central Jilin Province, China: Constraints from C–H–O and in–situ sulphur isotopes of pyrite and fluid inclusions - Jun-chi Chen; Ke-yong Wang; Xiang-jin Yan; Qing-ying Zhao; Li-Xue Sun (Geochemistry, 2024)

Cooperative S-S coupling and H2 production from photocatalytic dehydrogenation of thiols over ReSe2/ZnIn2S4 heterostructure - Xin Yang; Yanchao Jin; Sunzai Ke; Mengqing Li; Xuhui Yang; Lijuan Shen; Min-Quan Yang (Chemical Engineering Journal, 2024)

TEMDI: A Temporal Enhanced Multisource Data Integration model for accurate PM2.5 concentration forecasting - Ke Ren; Kangxu Chen; Chengyao Jin; Xiang Li; Yangxin Yu; Yiming Lin (Atmospheric Pollution Research, 2024)

Reconciled estimation of Antarctic ice sheet mass balance and contribution to global sea level change from 1996 to 2021 - Rongxing Li; Guojun Li; Gang Hai; Huan Xie; Yuan Cheng; Wei Chen; Xiangbin Cui; Minghu Ding; Chunchun Gao; Tong Hao; Changqing Ke; Chuanjin Li; et al. (Science China Earth Sciences, 2024)
The Antarctic Ice Sheet (AIS) has been losing ice mass and contributing to global sea level rise (GSLR). Given its mass that is enough to cause ∼58 m of GSLR, accurate estimation of mass balance trend is critical for AIS mass loss monitoring and sea level rise forecasting. Here, we present an improved approach to reconciled solutions of mass balance in AIS and its regions from multiple contributing solutions using the input-out, altimetric, and gravimetric methods. In comparison to previous methods, such as IMBIE 2018, this approach utilizes an adaptive data aggregation window to handle the heterogeneity of the contributing solutions, including the number of solutions, temporal distributions, uncertainties, and estimation techniques. We improved the regression-based method by using a two-step procedure that establishes ensembled solutions within each method (input-output, altimetry, or gravimetry) and then estimates the method-independent reconciled solutions. For the first time, 16 contributing solutions from 8 Chinese institutions are used to estimate the reconciled mass balance of AIS and its regions from 1996 to 2021. Our results show that AIS has lost a total ice mass of ∼3213±253 Gt during the period, an equivalent of ∼8.9±0.7 mm of GSLR. There is a sustained mass loss acceleration since 2006, from 88.1±3.6 Gt yr −1 during 1996–2005 to 130.7±8.4 Gt yr −1 during 2006–2013 and further to 157.0±9.0 Gt yr −1 during 2014–2021. The mass loss signal in the West Antarctica and Antarctic Peninsula is dominant and clearly presented in the reconciled estimation and contributing solutions, regardless of estimation methods used and fluctuation of surface mass balance. Uncertainty and challenges remain in mass balance estimation in East Antarctica. This reconciled estimation approach can be extended and applied for improved mass balance estimation in the Greenland Ice Sheet and mountain glacier regions.

The occurrence and biological control of zearalenone in cereals and cereal-based feedstuffs: a review - Hongmin Zhen; Yumeng Hu; Ke Xiong; Mengmeng Li; Wen Jin (Food Additives & Contaminants: Part A, 2024)

Prediction of adjacent single pile deformation induced by tunnel excavation based on the Pasternak model - Rui Wang; Bin Yan; You Wang; Ke-jin Li (Tunnelling and Underground Space Technology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Cytotoxic steroidal glycosides from Paris rugosa rhizomes - Jian-Ke Jia; Jun Yang; Xing-Zhi Yang; Ji-Feng Luo; Xiao-Yan Duan; Ying-Li Yang; Jin-Fu Wan; Yue-Hu Wang (Phytochemistry Letters, 2024)

Macroalgal fossil Longfengshania from the Tonian Shiwangzhuang and Jiuliqiao formations in western Shandong and northern Anhui, North China - Guang-Jin Li; Lei Chen; Ke Pang; Qing Tang; Cheng-Xi Wu; Rui Huang; Ming-Yang Qiu; Xun-Lai Yuan; Chuan-Ming Zhou (Palaeoworld, 2024)

CuS and polydopamine-modified polyvinyl alcohol foam for steady interfacial solar desalination of high saltwater - Chenxi Han; Youquan Li; Yibing Chen; Jin Zhang; Zijun Zhang; Yuqiu Ke; Jun Xiong; Linghui Yu; Ming Li (Journal of Environmental Chemical Engineering, 2024)

Quantification and modeling of disinfectant inactivation of Listeria monocytogenes biofilms on stainless steel surfaces - Hongmin Zhen; Yumeng Hu; Ke Xiong; Mengmeng Li; Wen Jin (Food Bioscience, 2024)

The influence mechanism of fulvic acid on Fe(II)-catalyzed transformation of Cr(III)-bearing schwertmannite: pH effect and nanoscale redistribution of Cr and C - Qian Yao; Limiao Cai; Xiaohu Jin; Xiaofei Li; Changdong Ke; Yirong Deng; Chuling Guo; Guining Lu; Zhi Dang; Xiaoyun Yi (Chemical Engineering Journal, 2024)

Applying Novel Micro–Nano-Siliceous Grouting Material Improves Mechanical Behaviors of Fractured Rock Masses and Microscopic Characteristics of Slurry–Rock Interface: Experimental and Numerical Simulation Investigations - Jin-Peng Zhang; Ke-Sheng Li; Yang Li; Chuan-Xiao Liu; Jun-Hao Xu; Jing-Ping He (Rock Mechanics and Rock Engineering, 2024)

Soil acidification drives the negative effects of nitrogen enrichment on soil microbial biomass at the global scale - Shucheng Li; Shiming Tang; Xiaotang Ju; Zhihao Zhu; Yujuan Zhang; Hongyang Chen; Ke Jin (Plant and Soil, 2024)

Neonicotinoid residues in fruits and vegetables in Shenzhen: Assessing human exposure and health risks - Xinjie Li; Sisi Yu; Ke Huang; Wenchao Zhu; Gang Ye; Jialiang Qi; Yanbo Shu; Xirui Chen; Zenghan Wang; Saiheidaiguli Maimaiti; Hongwei Jin; Shaoyou Lu (Chemosphere, 2024)

Divergent rainfall infiltration patterns on the Chinese Loess Plateau between growing and non-growing seasons after long-term revegetation - Ruoxuan Li; Bihang Fan; Zhao Jin; Mingkui Hao; Hu Liu; Yaling Zhang; Yanjia Jiang; Hongyu Yao; Ke Lin; Li Guo (Journal of Hydrology, 2024)

Enrichment mechanism of organic matter and silicon in lower Cambrian shale of the Yangtze Platform - Donglin Lin; Zhaodong Xi; Shuheng Tang; Gary G. Lash; Jin Li; Qiyang Gou; Ke Zhang; Xiaofan Mei; Kaifeng Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Contrasting responses of water use efficiency to increasing aridity in alpine shrubs: A modelling perspective - Menglin Su; Ke Yan; Xiangfu Wang; Jiaxin Jin; Yuanhui Li; Wenting Dong; Haikui Li; Jun Lu; Chuanchuan Zhao; Weifeng Wang (Journal of Hydrology, 2024)

Evolution of the rare-metal mineralization system associated with collision-related pegmatites in the western Altyn Tagh Orogen, Tugeman, NW China - Yince Ma; Tao Hong; Qiang Ke; Hang Li; Wenkai Jin; Zhiquan Yang; Peng Zhang; Zhaoxia Liao; Kai Kang; Chen Li; Decheng Ma; Xing-Wang Xu (Journal of Asian Earth Sciences, 2024)

A state-of-the-art review on the dynamic design of nonlinear energy sinks - Xiao-Feng Geng; Hu Ding; Jin-Chen Ji; Ke-Xiang Wei; Xing-Jian Jing; Li-Qun Chen (Engineering Structures, 2024)

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.

New alkaloids from Polygonatum zanlanscianense Pamp - Xue-Ke Zhang; Zhu-Zhen Han; Li Yang; Peng-Fei Zhang; Hong Zhang; Shou-Jin Liu (Natural Product Research, 2024)

Elucidating GO/iron series mediated stable flora and electron transfer under different COD/SO42− ratios - Ke Li; Qiliang Cao; Hui Zhang; Yuqi Jin; Qiaochu Liang; Huixia Lan; Wudi Zhang; Yang Zhang (Journal of Water Process Engineering, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Important roles of coarse particles in pasting and gelling performance of different pulse flours under high-temperature heating - Dong-Jin Lee; Fan Cheng; Dongxing Li; Ke Ding; Janelle Carlin; Emily Moore; Yongfeng Ai (Food Chemistry, 2024)

Construction of a plasmid-free Escherichia coli strain for lacto-N-neotetraose biosynthesis - Chao Liao; Xianhao Xu; Huiyuan Huang; Ruoqing Yang; Xuewen Zhu; Ke Jin; Yanfeng Liu; Jianghua Li; Guocheng Du; Xueqin Lv; Long Liu (Systems Microbiology and Biomanufacturing, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Non-destructive prediction of ready-to-eat kiwifruit firmness based on Fourier transform near-infrared spectroscopy - Gang Ding; Ke Jin; Xiaoya Chen; Ang Li; Zhiqiang Guo; Yunliu Zeng (Postharvest Biology and Technology, 2024)

Multiphase evolution of a Li-pegmatite field from the Tashisayi area, Altyn Tagh, NW China: insights from a petrological, geochemical, and geochronological study - Yin-Ce Ma; Xing-Wang Xu; Tao Hong; Wen-Kai Jin; Hang Li; Zhi-Quan Yang; Shan-Ke Liu; Kai Kang; Xue-Hai Wang; Lei Niu (Mineralium Deposita, 2024)

Effects of phosphorus limitation on sinking velocities of phytoplankton during summer in the Changjiang River Estuary - Xinchi You; Qiang Hao; Jie Zhu; Wei Zhang; Haiyan Jin; Dewang Li; Huanhong Ji; Yu Ke; Feng Zhou (Acta Oceanologica Sinica, 2024)

Tumor necrosis factor α1 decreases mucosal immune and antioxidant response in the midgut of hybrid fish (white crucian carp ♀ × red crucian carp ♂) - Ke‐Xin Li; Ning‐Xia Xiong; Jin‐Fang Huang; Shi‐Yun Li; Jie Ou; Fei Wang; Sheng‐Wei Luo (Journal of Fish Biology, 2024)
Tumor necrosis factor α1 (TNFα) is a pleiotropic cytokine involved in immune regulation and cellular homeostasis, but the crucial role of TNFα in fish gut remained unclear. The current study aimed to evaluate the immunoregulatory function of TNFα1 on gut barrier in a novel hybrid fish (WR), which was produced by crossing white crucian carp ( Carassius cuvieri , ♀) with red crucian carp ( Carassius auratus red var, ♂). In this study, WR ‐tnfα1 sequence was identified, and a high‐level expression was detected in the intestine. Elevated levels of WR ‐tnfα1 expressions were detected in immune‐related tissues and cultured fish cells on stimulation. The appearance of vacuolization and submucosal rupture was observed in TNFα1‐treated midgut of WR, along with elevated levels of goblet cell atrophy, whereas no significant changes were detected in most expressions of tight‐junction genes and mucin genes. In contrast, WR receiving gut perfusion with WR‐TNFα1 showed a remarkable decrease in antioxidant status in midgut, whereas the expression levels of apoptotic genes and redox responsive genes increased sharply. These results suggested that TNFα1 could exhibit a detrimental effect on antioxidant defense and immune regulation in the midgut of WR.

Effects of grazing on soil respiration in global grassland ecosystems - Shucheng Li; Tingting Xing; Rula Sa; Yujuan Zhang; Hongyang Chen; Ke Jin; Qingqin Shao; Shiming Tang; Chengjie Wang (Soil and Tillage Research, 2024)

Grazing alters the soil nematode communities in grasslands: A meta-analysis - Zhaokai Sun; Chongzhi Sun; Xin Feng; Tongrui Zhang; Jia Liu; Xinning Wang; Shucheng Li; Shiming Tang; Ke Jin (Journal of Environmental Management, 2024)

Diterpenoid alkaloids with chemotaxonomic significance from Aconitum polycarpum - Lin Chen; Jie Wen; Jia-Yi Ma; Ke Xu; Cheng-En Fu; Wen-Cheng Liang; Chen-Ying Zhu; Jin-Qiu Wang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2024)

Clinical characteristics and outcomes of COVID-19-associated encephalopathy in children - Li Li; Hongmei Liao; Xiaojun Kuang; Ke Jin (Journal of NeuroVirology, 2024)

Marine sulfated glycans inhibit the interaction of heparin with S-protein of SARS-CoV-2 Omicron XBB variant - Peng He; Yuefan Song; Weihua Jin; Yunran Li; Ke Xia; Seon Beom Kim; Rohini Dwivedi; Marwa Farrag; John Bates; Vitor H. Pomin; Chunyu Wang; Robert J. Linhardt; et al. (Glycoconjugate Journal, 2024)

Legacy effect of long-term rice–crab co-culture on N2O emissions in paddy soils - Weijing Li; Yibin Zhang; Hongyuan Wang; Bingqian Fan; Muhammad Amjad Bashir; Ke Jin; Hongbin Liu (Applied Soil Ecology, 2024)

Alleviating the adverse effects of Cd–Pb contamination through the application of silicon fertilizer: Enhancing soil microbial diversity and mitigating heavy metal contamination - Ke Ren; Xiongwei Yang; Jian Li; Hongyan Jin; Kaiyuan Gu; Yi Chen; Ming Liu; Yigui Luo; Yonglei Jiang (Chemosphere, 2024)

Organic nutrient availability and extracellular enzyme activities influence harmful algal bloom proliferation in a coastal aquaculture area - Lin-Jian Ou; Zhou Wang; Guang-Mao Ding; Feng-Xian Han; Jin-Yi Cen; Xin-Feng Dai; Ke-Qiang Li; Song-Hui Lu (Aquaculture, 2024)

Soil nitrogen availability drives the response of soil microbial biomass to warming - Shucheng Li; Shiming Tang; Hongyang Chen; Ke Jin (Science of The Total Environment, 2024)

Investigating the antibiotic resistance genes and their potential risks in the megacity water environment: A case study of Shenzhen Bay Basin, China - Hebin Liang; Jin Huang; Yi Tao; Uli Klümper; Thomas U. Berendonk; Kai Zhou; Yu Xia; Ying Yang; Yang Yu; Ke Yu; Lin Lin; Xiaoyan Li; et al. (Journal of Hazardous Materials, 2024)

Reference gene catalog and metagenome-assembled genomes from the gut microbiome reveal the microbial composition, antibiotic resistome, and adaptability of a lignocellulose diet in the giant panda - Shengzhi Yang; Wenwen Deng; Guo Li; Lei Jin; Yan Huang; Yongguo He; Daifu Wu; Desheng Li; Anyun Zhang; Chengxi Liu; Caiwu Li; Hemin Zhang; et al. (Environmental Research, 2024)

Sustainable management and valorization of biomass wastes using synthetic microbial consortia - Shi-Peng Zhou; Xia Ke; Li-Qun Jin; Ya-Ping Xue; Yu-Guo Zheng (Bioresource Technology, 2024)

Natural variation of Grain size 3 allele differentially functions in regulating grain length in xian/indica and geng/japonica rice - Yong-Bin Peng; Chen-Yang Du; Ya-Nan He; Chong-Ke Zheng; Wei Sun; Jin-Jun Zhou; Li-Xia Xie; Cong-Hui Jiang; Jian-Di Xu; Fang Wang; Xian-Zhi Xie (Euphytica, 2024)

Image-based vegetation analysis of desertified area by using a combination of ImageJ and Photoshop software - Jin Tong; Longying Wu; Bin Li; Nan Jiang; Jin Huang; Di Wu; Lihong Zhou; Qingwen Yang; Yuan Jiao; Ji Chen; Ke Zhao; Xiangjun Pei (Environmental Monitoring and Assessment, 2024)

Biological soil conditioner with reduced rates of chemical fertilization improves soil functionality and enhances rice production in vegetable-rice rotation - Ke Zhang; Haoyu Wei; Qi Chai; Lele Li; Yu Wang; Jin Sun (Applied Soil Ecology, 2024)

In Vitro Virulence Contrast of Seven Genetically Distinct Toxoplasma gondii Isolates After Rejuvenation In Vivo - Haiting Guo; Jie Tan; Yulin He; Shumin Yuan; Ke Jin; Zhongyuan Li (Acta Parasitologica, 2024)

RETRACTED: Applying thallium isotopic compositions as novel and sensitive proxy for Tl(I)/Tl(III) transformation and source apportionment - Juan Liu; Lulu Wang; Jingfen Lin; Wenhuan Yuan; Liangzhong Li; Yung-Kang Peng; Xinni Xiong; Huimin Cao; Xudong Wei; Qi'en Ouyang; Holger Lippold; Jin Wang; et al. (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

A transition from porphyry Mo to vein-style Zn-Pb mineralization: Insights from hydrothermal fluid evolution of the Chalukou deposit, NE China - Lu-Ying Jin; Ke-Zhang Qin; Brian Rusk; Jun-Xing Zhao; Zhen-Zhen Li; Guang-Ming Li; Guo-Xue Song (Journal of Asian Earth Sciences, 2024)

Development of a dual-functional inhibitor for natural gas hydrates and construction of drilling fluid system - Jintang Wang; Zhijun He; Yichen Yan; Lei Liu; Jin Yan; Bo Liao; Ke Zhao; Yiyao Li; Longqiao Chen (Gas Science and Engineering, 2024)

High-density lipoprotein cholesterol is associated with lowered cognitive recovery among acute ischemic stroke patients with mild cognitive impairment - Rui Wang; Zhuomin Jiao; Anxin Wang; Yijun Zhang; Xiangxiang Hong; Shan Huang; Jin Fu; Yinglian Zhou; Yifei Wang; Chunyang Li; Yue Liu; Ke Wei; et al. (Acta Neurologica Belgica, 2024)

Sirtuin 3-mediated deacetylation of superoxide dismutase 2 ameliorates sodium fluoride-induced mitochondrial dysfunction in porcine oocytes - Xin-Yue Qi; Jin-Dong Yuan; Zi-Yu Liu; Xi-Qing Jiang; Qi Zhang; Shan-Long Zhang; Lu Zhao; Ling-Yan Ke; Chen-Yuan Zhang; Yan Li; Lu-Yan Zhang; Qian-Qian Xu; et al. (Science of The Total Environment, 2024)

Microplastics enhance nitrogen loss from a black paddy soil by shifting nitrate reduction from DNRA to denitrification and Anammox - Xiaofang Ma; Jun Shan; Yanchao Chai; Zhijun Wei; Chenglin Li; Ke Jin; Han Zhou; Xiaoyuan Yan; Rong Ji (Science of The Total Environment, 2024)

Imine-vitrimer elastomer enabled triboelectric nanogenerators with remarkable electrical output and circular life cycles - Hongzhi Feng; Nannan Wang; Ke Li; Xiwei Xu; Binbo Wang; Yi Su; Bofan Li; Zibiao Li; Sheng Wang; Haiming Chen; Jin Zhu (Chemical Engineering Journal, 2024)

Large-area nanofiber membrane of NIR photothermal Cs0.32WO3 for flexible and all-weather solar thermoelectric generation - Sheng Zhuo; Wangkai Jiang; Yu Dong Zhao; Jin-Zhuo Liu; Xinyu Zhao; Jianyong Ye; Min Zheng; Zuo-Shan Wang; Xiao-Qing Zhou; Xiao-Qiao Wang; Ying-Li Shi; Weifan Chen; et al. (Chemical Engineering Journal, 2024)

Lead isotope compositions and modern sediments sources in the radial sand ridges from the Jiangsu coast, East China - Changping Mao; Wenbo Rao; Tianning Li; Ke Jin; Shuai Wang (Applied Geochemistry, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Surimi freshness monitoring of 4D printing material with anthocyanin - Jun-qi Zhan; Jing-jing Fu; Dan-li Jin; Yan-wei Yuan; Shi-ke Shen; Gao-shang Li; Yue-wen Chen (Journal of Food Engineering, 2023)

Alteration of microbial carbon and nitrogen metabolism within the soil metagenome with grazing intensity at semiarid steppe - Zhen Wang; Kai Tang; Paul C. Struik; Muhammad Nadeem Ashraf; Tongrui Zhang; Yanning Zhao; Riliga Wu; Ke Jin; Yuanheng Li (Journal of Environmental Management, 2023)

Discovery of the large-scale Eocene Xiwu Pb–Zn–Ag deposit in the Tethyan Himalaya: Geochronology, geochemistry, and C–H–O–S–Pb–Sr–Nd isotopes - Hua-Wen Cao; Qiu-Ming Pei; Xiao Yu; M. Santosh; Guang-Ming Li; Lin-Kui Zhang; Hao Zou; Lei Dong; Ke Gao; Zuo-Wen Dai; Jin-Biao Ai; Shuang-Shuang Lan; et al. (Gondwana Research, 2023)

P/N/S synergistic flame retardant holocellulose nanofibrils efficiently pretreated from ternary deep eutectic solvents - Jierui Ye; Yuebing Gao; Qingtian Xu; Zhenfu Jin; Guomin Wu; Siqun Wang; Zengkun Cai; Ke Yang; Qiang Wu; Qian Li (Chemical Engineering Journal, 2023)

Observations on the embryonic development of the mud crab, Scylla paramamosain - Li-Kun Xu; Ke-Yi Ma; Feng-Ying Zhang; Wei Wang; Ling-Bo Ma; Zhong-Wen Jin; Ming Zhao; Wei Chen; Yin Fu; Chun-Yan Ma; Zhi-Qiang Liu (Frontiers in Marine Science, 2023)
To investigate the embryonic development of the mud crab Scylla paramamosain , we analyzed three critical parameters: egg color of, embryo morphology (through conventional and laser scanning confocal microscopy), and the distribution of cell divisions. During embryonic development, the egg color exhibited a progressive transition, shifting from orange to reddish-orange, then to brown, before ultimately darkening to black. Each embryo displayed a spherical shape, measuring approximately 280 μm in diameter, characterized by a smooth surface devoid of any depressions. The embryonic cell division was in the form of mixed oogenesis, comprised of complete division in the early stage, spiral oogenesis in the middle stage and surface division in the late stage. It is noteworthy that the blastopore appeared at the position where the transparent area and cell aggregation just appeared under the microscope, and the blastomere was a characteristic of the embryo entering the gastrulation stage. After entering the gastrulation stage, the cells aggregated towards the blastopore and formed two symmetrical cell clusters, which formed a V-shape with the void of the classic blastopore. When the transparent region occupied approximately 1/5 of the embryo ’ s volume, the embryo entered the nauplius stage, and the thoracic and abdominal armor, as well as the optic lobe and abdominal limb primordia, could be clearly distinguished. The appearance of the compound eye pigment band indicated the stage of compound eye pigment formation. At this time, the transparent area accounted for 1/4 of the embryo and a large number of ganglia appeared. The change of the compound eye pigment band from red to black was also one of the reasons for the blackening of the egg color of the crabs. The data obtained through this study have potential applications in the determination of embryonic development status and obtaining of high-quality seeds for S. paramamosain culture.

Trends in air pollutants emissions in the Qinghai-Tibet Plateau and its surrounding areas under different socioeconomic scenarios - Ke Jiang; Ran Xing; Zhihan Luo; Jin Li; Yatai Men; Huizhong Shen; Guofeng Shen; Shu Tao (Science of The Total Environment, 2023)

Gastrointestinal microbiome, resistance genes, and risk assessment of heavy metals in wild giant pandas - Lei Jin; Hongning Wu; Guo Li; Shengzhi Yang; Rongping Wei; Yan Huang; Petri Penttinen; Wenwen Deng; Jianbin Chen; Xinfeng Han; Caiwu Li; Lan Hu; et al. (Science of The Total Environment, 2023)

Numerical analysis of wake field and unsteady forces on submarine propeller with twisted rudders - Jin-ming Ye; Di Zhang; Zi-han Zheng; Wan-li Yang; Lin Ke (Ocean Engineering, 2023)

Extraction of triterpene acids from loquat leaves via a novel hydrophobic deep eutectic solvent screened by COSMO-SAC model - Lu Huang; Yingjie Guo; Tianqi Jin; Ke Yan; Xianglin Liu; Shuyang He; Lin Li; Ye Gong; Junyi Ma; Hang Yu; Zhoumin Lu; Yupeng Liu; et al. (Journal of Cleaner Production, 2023)

ALPK1 Expressed in IB4-Positive Neurons of Mice Trigeminal Ganglions Promotes MIA-Induced TMJ pain - Taomin Zhu; Huimin Li; Yuxiang Chen; Xueke Jia; Xiaohan Ma; Xin Liu; Yaping Feng; Jin Ke (Molecular Neurobiology, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Heavy metals and Pb isotopes in sediment cores from the Bering and Chukchi seas: Implications for environmental changes and human activities over the past century - Yan Lin; Zhai Wu; Hongwei Ke; Huorong Chen; Ye Xu; Jin Lin; Yanguang Liu; Fangjian Xu; Dongren Huang; Yi Wang; Tianyao Li; Minggang Cai (Marine Environmental Research, 2023)

Discovery of new strains for furfural degradation using adaptive laboratory evolution in Saccharomyces cerevisiae - Hanyu Wang; Qian Li; Zhengyue Zhang; Ellen Ayepa; Quanju Xiang; Xiumei Yu; Ke Zhao; Likou Zou; Yunfu Gu; Xi Li; Qiang Chen; Xiaoping Zhang; et al. (Journal of Hazardous Materials, 2023)

Electronic modulation of S and N co-implanted carbon as fenton-like photocatalysts for water remediation - Xin Li; Wendan Luo; Ke Zhu; Yuwen Chen; Yizhe Huang; Chao Jin; Rongliang Qiu; Shaojuan Luo; Guoqing Guan; Kai Yan (Chemical Engineering Journal, 2023)

CNIH4 governs cervical cancer progression through reducing ferroptosis - Jun-Yuan Yang; Dong Ke; Yanli Li; Jie Shi; Shi-Meng Wan; An-Jin Wang; Meng-Na Zhao; Han Gao (Chemico-Biological Interactions, 2023)

Recovery through proper grazing exclusion promotes the carbon cycle and increases carbon sequestration in semiarid steppe - Wenbo Zhang; Jing Li; Paul C. Struik; Ke Jin; Baoming Ji; Shengyi Jiang; Yong Zhang; Yuanheng Li; Xiaojiang Yang; Zhen Wang (Science of The Total Environment, 2023)

Rapid and user-friendly detection of selenium-rich foods using a THEATER colorimetric device with Pt-Co-N-C as viewing glasses - Yang Chen; Tianyi Ma; Ruiqing Ke; Mengyu Lu; Jiaxing An; Yijia Wang; Kunlun Huang; Yunbo Luo; Jin-Cheng Li; Nan Cheng (Chemical Engineering Journal, 2023)

Experimental investigation of buoyancy effects on the heat transfer of supercritical carbon dioxide in a vertical tube - Yixuan Jin; Pinghui Zhao; Teng Wan; Zhansheng Chen; Ke Liu; Xiaohu Wang; Yuanjie Li; Yuanxi Wan (Annals of Nuclear Energy, 2023)

Peroxymonosulfate activation by Fe-N-S co-doped tremella-like carbocatalyst for degradation of bisphenol A: Synergistic effect of pyridine N, Fe-Nx, thiophene S - Wenjin Chen; Lele Lei; Ke Zhu; Dongdong He; Hongmei He; Xiulan Li; Yumeng Wang; Jin Huang; Yushi Ai (Journal of Environmental Sciences, 2023)

Insights into the modulation of the multi-scale structure of glutelin on the textural properties of reconstituted rice - Li-Shuang Wang; Xiao-Shuai Yu; Ke-Xin Wang; Jin-Jie Huo; Xiao-Qi Ma; Yu-Min Duan; Zhi-Gang Xiao; Peng Wang (Innovative Food Science & Emerging Technologies, 2023)

In vitro digestion and fermentation combined with microbiomics and metabolomics reveal the mechanism of superfine yak bone powder regulating lipid metabolism by altering human gut microbiota - Jin Zhang; Xiaoqiong Li; Ke Zhao; Huanhuan Li; Jingnan Liu; Se Da; Dajie Ciren; Honggang Tang (Food Chemistry, 2023)

Isochromenes from the Nicotiana tabacum -derived endophytic fungus Aspergillus versicolor and their anti-tobacco mosaic virus activities - Feng-Xian Yang; Jia-Meng Dai; Hua-Yin Liu; Qi-Li Mi; Jin Wang; Jian-Duo Zhang; Xue-Mei Li; Wei-Guang Wang; Min Zhou; Yin-Ke Li; Qiu-Fen Hu (Natural Product Research, 2023)

Different behaviors of organic matter under physical-biological controls in the eastern Indian Ocean - Yixue Zhang; Ying Wu; Jing Zhang; Yi Xu; Ke Huang; Jie Jin; Jinlong Dai; Qi Ye; Jian Li; Zhenqiu Zhang (Frontiers in Marine Science, 2023)
Marine organic matter (OM) pools are the key to understanding biogeochemical cycles and carbon storage, especially under ongoing ocean warming. The tropical eastern Indian Ocean (IO) is ideal for unraveling marine OM pools for being one of the least understood ocean basins in terms of its complex physical and biogeochemical dynamics. So far, OM transformation and export remain underexplored and enigmatic in the IO. Here, we integrated in situ observations and incubation experiments in the Central IO (CIO) and Bay of Bengal (BoB). A large OM pool was found in the CIO, where we emphasized the prominent contribution of production in the deep euphotic layer, with physical forcing seasonally playing a supporting role. The dissolved organic matter (DOM)-degradation experiment results revealed high efficiency of in situ DOM consumption in the BoB, whereas dark carbon fixation by ammonia-oxidizing microorganisms was considered an alternative strategy in the euphotic CIO. Water mixing was found to highly influence the OM pools in the mesopelagic waters in the tropical eastern IO, but active microbial respiration could also regulate the OM degradation in the CIO. Our results emphasized the heterogeneity of OM pools between the BoB and CIO, and stated their different regulators of carbon reservoir considering an ocean warming scenario.

Effects of chitosan coating combined with thermal treatment on physicochemical properties, bacterial diversity and volatile flavor of braised duck meat during refrigerated storage - Huanhuan Li; Sijia Qu; Ping Ma; Jin Zhang; Ke Zhao; Lihong Chen; Qicheng Huang; Gaohang Zou; Honggang Tang (Food Research International, 2023)

Fabrication of an alginate-based ZhiNengCong gel showed an enhanced antiviral and plant growth promoting functions - Long Jiang; Qin Wang; Shuai Zhang; Changyun Liu; Ke Wang; Fengwei Li; Xiaoyan Wang; Weina Liu; Xiaozhou Ma; Guangjin Fan; Tiancai Chen; Yabo Jin; et al. (Pesticide Biochemistry and Physiology, 2023)

Combinatorial metabolic engineering enables the efficient production of ursolic acid and oleanolic acid in Saccharomyces cerevisiae - Ke Jin; Xun Shi; Jiaheng Liu; Wenwen Yu; Yanfeng Liu; Jianghua Li; Guocheng Du; Xueqin Lv; Long Liu (Bioresource Technology, 2023)

A comprehensive drought index based on remote sensing data and nested copulas for monitoring meteorological and agroecological droughts: A case study on the Qinghai-Tibet Plateau - Yujia Cheng; Ke Zhang; Lijun Chao; Wuzhi Shi; Jin Feng; Yunping Li (Environmental Modelling & Software, 2023)

Catalytic activation of peroxydisulfate by secondary mineral derived self-modified iron-based composite for florfenicol degradation: Performance and mechanism - Ke Zhang; Quanliu Yang; Yuwen Jin; Peng He; Qiongyao Li; Pan Chen; Jianyu Zhu; Min Gan (Chemosphere, 2023)

Effect of gadopentetate dimeglumine on bone growth in zebrafish caudal fins - Rongbiao Tang; Yi Chen; Naying He; Yan Li; Zhijia Jin; Ke-Min Chen; Fuhua Yan (Toxicology Letters, 2023)

Two new terpenoids and other constituents from Salvia cavaleriei and their antibacterial activities - Yu-Min Zhao; Ke Li; Han-Fei Liu; Jin-Yu Li; Jian Fu; Hua-Yong Lou; Wei-Dong Pan (Phytochemistry Letters, 2023)

Experimental study on alkali catalytic gasification of oily sludge in supercritical water with a continuous reactor - Linhu Li; Gaoyun Wang; Xujun Li; Le Wang; Jiawei Zhang; Ke Cheng; Pai Peng; Wen Cao; Hui Jin; Liejin Guo (Journal of Environmental Management, 2023)

Localizing electrons on atomic platinum by metal phosphides for accelerating electrocatalytic hydrogen evolution - Dayong Ren; Guowei Wang; Leyuan Li; Yuhong Jin; Kailing Zhou; Chuitao Zeng; Qianqian Zhang; Jingbing Liu; Ruzhi Wang; Xiaoxing Ke; Manling Sui; Hao Wang (Chemical Engineering Journal, 2023)

Sulfuretted Li- and Mn-rich cathode material with epitaxial spinel stabilizer for ultra-long cycle Li-ion battery - Wanyun Li; Bangchuan Zhao; Jin Bai; Hongyang Ma; Peiyao Wang; Yunjie Mao; Ke Xiao; Xuelian Wang; Peng Tong; Xuebin Zhu; Yuping Sun (Chemical Engineering Journal, 2023)

Analysis of Whole Blood and Urine Trace Elements in Children with Autism Spectrum Disorders and Autistic Behaviors - Gang Zhao; Si-jin Liu; Xin-yu Gan; Jun-ru Li; Xiao-xue Wu; Si-yan Liu; Yi-si Jin; Ke-rang Zhang; Hong-mei Wu (Biological Trace Element Research, 2023)
The relationship between trace elements and neurological development is an emerging research focus. We performed a case–control study to explore (1) the differences of 13 trace elements chromium (Cr), manganese (Mn), cobalt (Co), zinc (Zn), arsenic (As), selenium (Se), molybdenum (Mo), cadmium (Cd), stannum (Sn), stibium (Sb), mercury (Hg), titanium (TI), and plumbum (Pb) concentration in whole blood and urine between autism spectrum disorder (ASD) children and their typical development peers, and (2) the association between the 13 trace elements and core behaviors of ASD. Thirty ASD subjects (cases) and 30 age-sex-matched healthy subjects from Baise City, Guangxi Zhuang Autonomous Region, China, were recruited. Element analysis was carried out by inductively coupled plasma-optical emission spectrometry. Autistic behaviors were assessed using Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), and Children Neuropsychological and Behavior Scale (CNBS). The whole blood concentrations of Mo ( p = 0.004), Cd (0.007), Sn ( p = 0.003), and Pb ( p = 0.037) were significantly higher in the ASD cases than in the controls. Moreover, Se (0.393), Hg (0.408), and Mn (− 0.373) concentrations were significantly correlated between whole blood and urine levels in ASD case subjects. There were significant correlations between whole blood Sb (0.406), Tl (0.365), Mo (− 0.4237), Mn (− 0.389), Zn (0.476), and Se (0.375) levels and core behaviors of ASD. Although the mechanism of trace element imbalance in ASD is unclear, these data demonstrate that core behaviors of ASD may be affected by certain trace elements. Further studies are recommended for exploring the mechanism of element imbalance and providing corresponding clinical treatment measures.

The anti-TMV potency of the tobacco-derived fungus Aspergillus versicolor and its active alkaloids, as anti-TMV activity inhibitors - Jia-Meng Dai; Qi-Li Mi; Xue-Mei Li; Du Gang; Guang-Yu Yang; Jian-Duo Zhang; Jin Wang; Yin-Ke Li; Hai-Ying Yang; Dong Miao; Zhen-Jie Li; Qiu-Fen Hu (Phytochemistry, 2023)

Scaling-up and proteomic analysis reveals photosynthetic and metabolic insights toward prolonged H2 photoproduction in Chlamydomonas hpm91 mutant lacking proton gradient regulation 5 (PGR5) - Peng Liu; De-Min Ye; Mei Chen; Jin Zhang; Xia-He Huang; Li-Li Shen; Ke-Ke Xia; Xiao-Jing Xu; Yong-Chao Xu; Ya-Long Guo; Ying-Chun Wang; Fang Huang (Photosynthesis Research, 2022)
Clean and sustainable H 2 production is crucial to a carbon–neutral world. H 2 generation by Chlamydomonas reinhardtii is an attractive approach for solar-H 2 from H 2 O. However, it is currently not large-scalable because of lacking desirable strains with both optimal H 2 productivity and sufficient knowledge of underlying molecular mechanism. We hereby carried out extensive and in-depth investigations of H 2 photoproduction of hpm91 mutant lacking PGR5 (Proton Gradient Regulation 5) toward its up-scaling and fundamental mechanism issues. We show that hpm91 is at least 100-fold scalable (up to 10 L) with continuous H 2 collection of 7287 ml H 2 /10L-HPBR in averagely 26 days under sulfur deprivation. Also, we show that hpm91 is robust and active during sustained H 2 photoproduction, most likely due to decreased intracellular ROS relative to wild type. Moreover, we obtained quantitative proteomic profiles of wild type and hpm91 at four representing time points of H 2 evolution, leading to 2229 and 1350 differentially expressed proteins, respectively. Compared to wild type, major proteome alterations of hpm91 include not only core subunits of photosystems and those related to anti-oxidative responses but also essential proteins in photosynthetic antenna, C/N metabolic balance, and sulfur assimilation toward both cysteine biosynthesis and sulfation of metabolites during sulfur-deprived H 2 production. These results reveal not only new insights of cellular and molecular basis of enhanced H 2 production in hpm91 but also provide additional candidate gene targets and modules for further genetic modifications and/or in artificial photosynthesis mimics toward basic and applied research aiming at advancing solar-H 2 technology.

Environmental Factors Controlling Dissimilatory Nitrate Reduction to Ammonium in Paddy Soil - Zhijun Wei; Ke Jin; Chenglin Li; Min Wu; Jun Shan; Xiaoyuan Yan (Journal of Soil Science and Plant Nutrition, 2022)

Energy substrate metabolism and oxidative stress in metabolic cardiomyopathy - Ze Chen; Zhao-Xia Jin; Jingjing Cai; Ruyan Li; Ke-Qiong Deng; Yan-Xiao Ji; Fang Lei; Huo-Ping Li; Zhibing Lu; Hongliang Li (Journal of Molecular Medicine, 2022)

The cAMP‐PKA signalling pathway regulates hyphal growth, conidiation, trap morphogenesis, stress tolerance, and autophagy in Arthrobotrys oligospora - Mei‐Chen Zhu; Na Zhao; Yan‐Kun Liu; Xue‐Mei Li; Zheng‐Yi Zhen; Ya‐Qing Zheng; Ke‐Qin Zhang; Jin‐Kui Yang (Environmental Microbiology, 2022)
The cyclic adenosine monophosphate‐protein kinase A (cAMP‐PKA) signalling pathway is evolutionarily conserved in eukaryotes and plays a crucial role in defending against external environmental challenges, which can modulate the cellular response to external stimuli. Arthrobotrys oligospora is a typical nematode‐trapping fungus that specializes in adhesive networks to kill nematodes. To elucidate the biological roles of the cAMP‐PKA signalling pathway, we characterized the orthologous adenylate cyclase AoAcy, a regulatory subunit (AoPkaR), and two catalytic subunits (AoPkaC1 and AoPkaC2) of PKA in A. oligospora by gene disruption, transcriptome, and metabolome analyses. Deletion of Aoacy significantly reduced the levels of cAMP and arthrobotrisins. Results revealed that Aoacy , AopkaR , and AopkaC1 were involved in hyphal growth, trap morphogenesis, sporulation, stress resistance, and autophagy. In addition, Aoacy and AopkaC1 were involved in the regulation of mitochondrial morphology, thereby affecting energy metabolism, whereas AopkaC2 affected sporulation, nuclei, and autophagy. Multi‐omics results showed that the cAMP‐PKA signalling pathway regulated multiple metabolic and cellular processes. Collectively, these data highlight the indispensable role of cAMP‐PKA signalling pathway in the growth, development, and pathogenicity of A. oligospora, and provide insights into the regulatory mechanisms of signalling pathways in sporulation, trap formation, and lifestyle transition.

Mulberry leaf extract improves non-specific immunity and antioxidant capacity of largemouth bass (Micropterus salmoides) fed a high-starch diet - Jing Tingsen; Luo Hui; Huang Junwa; Li Zhe; Li Yu; Jin Honghao; Zou Xinxi; Ke Zhenlin; Sun Wenbo; Hou Mengdan; Yang Huijun; Ye Hua (Frontiers in Marine Science, 2022)
A 70-day experiment was conducted to investigate the effects of mulberry leaf extract (MLE) on growth, proximate compositions, antioxidant and plasma biochemical parameters, and indices of non-specific immunity of largemouth bass ( Micropterus salmoides ) fed a high-starch diet. Two hundred eighty largemouth bass (initial body weight, 68.00 ± 0.19 g) were randomly fed seven diets: basal-starch diet (BSD; 8.88% starch), high-starch diet (HSD; 11.42% starch), and HSD diets supplemented with 0.05%, 0.10%, 0.20%, 0.50%, and 1.00% MLE (MLE1, MLE2, MLE3, MLE4, and MLE5, respectively). The results indicated that HSD and MLE did not significantly affect the growth performance of largemouth bass during the experimental period compared with that of the BSD, but the supplementation with more than 0.20% (MLE3, MLE4, and MLE5) MLE significantly decreased the hepatosomatic index (HSI) values, and 1.00% (MLE5) MLE significantly decreased the viscerosomatic index (VSI) values. The whole-body moisture of fish fed an HSD decreased significantly, while the whole-body lipid content increased significantly in the HSD group compared with the BSD group. Compared with HSD, MLE supplementation significantly decreased the moisture and lipid contents in the whole body. Supplementation with more than 0.20% MLE (MLE3, MLE4, and MLE5) significantly decreased the moisture content in the muscle. Supplementation with 1.00% MLE significantly decreased the content of hepatic and muscle glycogen. The malondialdehyde (MDA) content of the HSD group was significantly increased compared to that of the BSD group, whereas more than 0.10% (MLE2, MLE3, MLE4, and MLE5) MLE significantly decreased the MDA content. Additionally, the total antioxidant capacity (T-AOC), catalase (CAT), and glutathione peroxidase (GSH-Px) activities of MLE5 were significantly higher than those of the HSD group. The complement-3 (C3) content and globulin (GLB) in the plasma of the HSD group were significantly lower than those of the BSD group. Plasma C3 levels in the MLE3, MLE4, and MLE5 groups were significantly higher than those in the HSD group. In addition, glucose (GLU) levels in the MLE3, MLE4, and MLE5 groups were significantly lower than those in the HSD group. Supplementation with 0.50% (MLE4) MLE significantly increased the lysozyme (LYZ) content and decreased the activities of alanine transaminase (ALT) and aspartate transaminase (AST). Supplementation with 1.00% MLE significantly increased complement-4 (C4) and GLB contents and alkaline phosphatase (ALP) activity. Overall, these findings suggest that MLE could improve antioxidant capacity, immune function, and glycolipid metabolism, thereby alleviating the negative effects of a high-starch diet in M. salmoides .

The impact of low-carbon city pilot policy on green total-factor productivity in China’s cities - Ke-Liang Wang; Jin Li; Ru-Yu Xu; Su-Qin Pang; Zhuang Miao; Hua-Ping Sun (Environmental Science and Pollution Research, 2022)

Tumor necrosis factor-α coordinates with transforming growth factor-β1 to induce epithelial-mesenchymal transition and migration via the NF-κB/NOX4 pathway in bronchial epithelial cells - Ke Li; Rong Zhou; Mingze Ma; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Fang Zhou (Molecular Biology Reports, 2022)

Transcriptome analysis and co‐expression network reveal the mechanism linking mitochondrial function to immune regulation in red crucian carp ( Carassius auratus red var) after Aeromonas hydrophila challenge - Ning‐Xia Xiong; Xu‐Ying Kuang; Zi‐Xuan Fang; Jie Ou; Shi‐Yun Li; Jia‐Hui Zhao; Jin‐Fang Huang; Ke‐Xin Li; Rou Wang; Lan‐Fen Fan; Sheng‐Wei Luo; Shao‐Jun Liu (Journal of Fish Diseases, 2022)
Aeromonas hydrophila is a common pathogen of freshwater fish. In this study, A. hydrophila infection was shown to cause tissue damage, trigger physiological changes as well as alter the expression profiles of immune‐ and metabolic‐related genes in immune tissues of red crucian carp (RCC). Transcriptome analysis revealed that acute A. hydrophila infection exerted a profound effect on mitochondrial oxidative phosphorylation linking metabolic regulation to immune response. In addition, we further identified cellular senescence, apoptosis, necrosis and mitogen‐activated protein kinase signal pathways as crucial signal pathways in the kidney of RCC subjected to A. hydrophila infection. These findings may have important implications for understanding modulation of immunometabolic response to bacterial infection.

Stat5−/− CD4+ T cells elicit anti-melanoma effect by CD4+ T cell remolding and Notch1 activation - Ke Jin; Tong Li; Zhiyong Miao; Jingjing Ran; Luyu Chen; Dachao Mou; Chuang Wang; Shasha Wu; Hanshuo Yang; Xin-Yuan Fu (Science China Life Sciences, 2022)

Super Stability of Cu-Mn/Y Bimetallic Catalyst for Ozone-assisted Catalytic Oxidation of Toluene - Ke Xia; Jin-Hua Huang; Li-Ping Ye (Water, Air, & Soil Pollution, 2022)

Intrauterine hyperglycemia impairs endometrial receptivity via up-regulating SGK1 in diabetes - Haiyan Xu; Jingyi Li; Luyang Jin; Dan Zhang; Bin Chen; Xinmei Liu; Xianhua Lin; Yiting Huang; Zhanghong Ke; Juan Liu; Lin Gao; Jianzhong Sheng; et al. (Science China Life Sciences, 2022)

The traditional uses, secondary metabolites, and pharmacology of Eleutherococcus species - Yue-Hui Huang; Jin-Tao Li; Ke Zan; Jun Wang; Qiang Fu (Phytochemistry Reviews, 2022)

High glucose-induced ROS-accumulation in embryo-larval stages of zebrafish leads to mitochondria-mediated apoptosis - Yaoqi Li; Qianqian Chen; Yinai Liu; Liuliu Bi; Libo Jin; Ke Xu; Renyi Peng (Apoptosis, 2022)

Predicting long-term hydrological change caused by climate shifting in the 21st century in the headwater area of the Yellow River Basin - Jingyi Hu; Yiping Wu; Pengcheng Sun; Fubo Zhao; Ke Sun; Tiejian Li; Bellie Sivakumar; Linjing Qiu; Yuzhu Sun; Zhangdong Jin (Stochastic Environmental Research and Risk Assessment, 2022)

FLO8 deletion leads to decreased adhesion and virulence with downregulated expression of EPA1, EPA6, and EPA7 in Candida glabrata - Jun-Tao Zhao; Ke-Zhi Chen; Jin-Yan Liu; Wei-Hua Li; Yu-Zhu Wang; Lu-Ling Wang; Ming-Jie Xiang (Brazilian Journal of Microbiology, 2022)

Comparison of different inversion methods of D-T2 two-dimensional nuclear magnetic resonance logging and applicability analysis - Cheng-Lin Li; Mao-Jin Tan; Ke-Wen Wang; Feng Zhou; Ying-Ming Liu; Hai-Tao Zhang; Li-Zhi Xiao (Applied Geophysics, 2022)

Positive microbial legacy and short-term clonal plasticity aid grazing tolerance of a widespread grass species - Xiliang Li; G. Kenny Png; Shixian Sun; Hongxiao Shi; Ke Jin; Yuanheng Li (Plant and Soil, 2022)

Genetic diversity and population structure of Curcuma alismatifolia Gagnep. accessions revealed by SSR markers - Hui-Wen Yu; Ling-Jun Ke; Yi-Lan Xiao; Si-Jia Chen; Yuan-Yuan Li; Qi-Lin Tian; Yun-He Li; Jin-Shui Lin; Luan-Mei Lu (Genetic Resources and Crop Evolution, 2022)

Expansion of bilin‐based red light sensors in the subaerial desert cyanobacterium Nostoc flagelliforme - Hai‐Feng Xu; Guo‐Zheng Dai; Yu‐Jie Wang; Chao Cheng; Jin‐Long Shang; Ren‐Han Li; Ke Liu; Deqiang Duanmu; Bao‐Sheng Qiu (Environmental Microbiology, 2022)
Summary Light is the crucial environmental signal for desiccation‐tolerant cyanobacteria to activate photosynthesis and prepare for desiccation at dawn. However, the photobiological characteristics of desert cyanobacteria adaptation to one of the harshest habitats on Earth remain unresolved. In this study, we surveyed the genome of a subaerial desert cyanobacterium Nostoc flagelliforme and identified two phytochromes and seven cyanobacteriochromes (CBCRs) with one or more bilin‐binding GAF (cGMP phosphodiesterase/adenylyl cyclase/FhlA) domains. Biochemical and spectroscopic analyses of 69 purified GAF‐containing proteins from recombinant phycocyanobilin (PCB), biliverdin or phycoerythrobilin‐producing Escherichia coli indicated that nine of these proteins bind chromophores. Further investigation revealed that 11 GAFs form covalent adducts responsive to near‐UV and visible light: eight GAFs contained PCB chromophores, three GAFs contained biliverdin chromophores and one contained the PCB isomer, phycoviolobilin. Interestingly, COO91_03972 is the first‐ever reported GAF‐only CBCR capable of sensing five wavelengths of light. Bioinformatics and biochemical analyses revealed that residue P132 of COO91_03972 is essential for chromophore binding to dual‐cysteine CBCRs. Furthermore, the complement of N . flagelliforme CBCRs is enriched in red light sensors. We hypothesize that these sensors are critical for the acclimatization of N . flagelliforme to weak light environments at dawn.

Transcriptomic and physiological analysis reveals interplay between salicylic acid and drought stress in citrus tree floral initiation - Faiza Shafique Khan; Zhi-Meng Gan; En-Qing Li; Meng-Ke Ren; Chun-Gen Hu; Jin-Zhi Zhang (Planta, 2022)

Levels of polycyclic aromatic hydrocarbons in edible and fried vegetable oil: a health risk assessment study - Jin-Kui Ma; Ke Li; Xiang Li; Seham Elbadry; Amal A. Raslan; Yan Li; Zohair S. Mulla; Asmaa B. M. B. Tahoun; Waleed Rizk El-Ghareeb; Xiao-Chen Huang (Environmental Science and Pollution Research, 2021)

Gut-Derived Exosomes Mediate Memory Impairment After Intestinal Ischemia/Reperfusion via Activating Microglia - Xiao-Dong Chen; Jin Zhao; Xiao Yang; Bo-Wei Zhou; Zhengzheng Yan; Wei-Feng Liu; Cai Li; Ke-Xuan Liu (Molecular Neurobiology, 2021)

Application of constructed wetlands in treating rural sewage from source separation with high-influent nitrogen load: a review - Xiangyu Li; Longjian Yang; Kaiqin Xu; Ke Bei; Xiangyong Zheng; Shiwen Lu; Ning An; Jinshan Zhao; Zhan Jin (World Journal of Microbiology and Biotechnology, 2021)

Antimicrobial nanomedicine for ocular bacterial and fungal infection - Wenjie Fan; Haijie Han; Yaoyao Chen; Xiaobo Zhang; Yifan Gao; Su Li; Qiao Jin; Jian Ji; Ke Yao (Drug Delivery and Translational Research, 2021)

Diversity and Composition of Gut Bacterial Community in Giant Panda with Anorexia - Siyue Zhao; Caiwu Li; Tao Zhu; Lei Jin; Wenwen Deng; Ke Zhao; Yongguo He; Guo Li; Yaowu Xiong; Ti Li; Bei Li; Yan Huang; et al. (Current Microbiology, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

Primary fluid exsolution in porphyry copper systems: evidence from magmatic apatite and anhydrite inclusions in zircon - Jin-Xiang Li; Guang-Ming Li; Noreen J. Evans; Jun-Xing Zhao; Ke-Zhang Qin; Jing Xie (Mineralium Deposita, 2021)

Conserving the Chinese caterpillar fungus under climate change - Yi Li; Yujing Yan; Zhiyao Tang; Ke Wang; Jin-Sheng He; Yi-Jian Yao (Biodiversity and Conservation, 2021)

Community structure of bacterioplankton and its relationship with environmental factors in the upper reaches of the Heihe River in Qinghai Plateau - Zhang Qian‐Qian; Jian Sheng‐Long; Li Ke‐Mao; Wu Zhen‐Bing; Guan Hong‐Tao; Hao Jin‐Wen; Wang Shu‐Yi; Lin Yao‐Yao; Wang Guo‐Jie; Li Ai‐Hua (Environmental Microbiology, 2021)
Summary Planktonic microorganisms play a key role in the biogeochemical processes of the aquatic system, and they may be affected by many factors. High‐throughput sequencing technology was used in this study to investigate and study the bacterioplankton community of water bodies in the upper reaches of the Heihe River Basin in Qinghai Plateau. Results showed that Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria are the predominant phyla in this river section, while the main genera are Thiomonas , Acidibacillus , Acidocella , Rhodanobacter , Acidithiobacter and Gallionella , which are autochthonous in the acid‐mine drainage. Additionally, total nitrogen, total phosphorus, permanganate index and pH are significantly correlated with the bacterioplankton abundance and are the main limiting factors for the spatial distribution of the bacterioplankton. PICRUSt inferred that the mainstream microbial assemblages had a higher abundance of KOs belong to metabolism of terpenoids and polyketides, while the tributary had higher abundance of KOs belong to the immune system. The relationship between bacterioplankton community composition and environmental factors in the Heihe River basin was discussed for the first time in this study, which provides a theoretical basis for the healthy, orderly development of the water environment in the Heihe River Basin.

Correction to: Analysis of the complete genome sequence of a potyvirus from passion fruit suggests its taxonomic classification as a member of a new species - Ke Yang; Haixia Yan; Li Song; Pengfei Jin; Weiguo Miao; Hongguang Cui (Archives of Virology, 2021)

A unique porin meditates iron‐selective transport through cyanobacterial outer membranes - Guo‐Wei Qiu; Hai‐Bo Jiang; Hagar Lis; Zheng‐Ke Li; Bin Deng; Jin‐Long Shang; Chuan‐Yu Sun; Nir Keren; Bao‐Sheng Qiu (Environmental Microbiology, 2021)
Summary Cyanobacteria are globally important primary producers and nitrogen fixers with high iron demands. Low ambient dissolved iron concentrations in many aquatic environments mean that these organisms must maintain sufficient and selective transport of iron into the cell. However, the nature of iron transport pathways through the cyanobacterial outer membrane remains obscure. Here we present multiple lines of experimental evidence that collectively support the existence of a novel class of substrate‐selective iron porin, Slr1908, in the outer membrane of the cyanobacterium Synechocystis sp. PCC 6803. Elemental composition analysis and short‐term iron uptake assays with mutants in Slr1908 reveal that this protein is primarily involved in inorganic iron uptake and contributes less to the accumulation of other metals. Homologues of Slr1908 are widely distributed in both freshwater and marine cyanobacteria, most notably in unicellular marine diazotrophs. Complementary experiments with a homologue of Slr1908 in Synechococcus sp. PCC 7002 restored the phenotype of Synechocystis knockdown mutants, showing that this siderophore producing species also possesses a porin with a similar function in Fe transport. The involvement of a substrate‐selective porins in iron uptake may allow cyanobacteria to tightly control iron flux into the cell, particularly in environments where iron concentrations fluctuate.

Epitranscriptomic technologies and analyses - Xiaoyu Li; Qiao-Xia Liang; Jin-Ran Lin; Jinying Peng; Jian-Hua Yang; Chengqi Yi; Yang Yu; Qiangfeng Cliff Zhang; Ke-Ren Zhou (Science China Life Sciences, 2020)

Response of bacterial communities and plant-mediated soil processes to nitrogen deposition and precipitation in a desert steppe - Zhen Wang; Risu Na; Liz Koziol; Michael P. Schellenberg; Xiliang Li; Na Ta; Ke Jin; Hai Wang (Plant and Soil, 2020)

An ɑ 2 -adrenergic receptor is involved in larval metamorphosis in the mussel, Mytilus coruscus - Xiao Liang; Ke Chen; Yi-Feng Li; Wei-Yang Bao; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang (Biofouling, 2019)

Genome-wide survey and expression analyses of the GRAS gene family in Brassica napus reveals their roles in root development and stress response - Pengcheng Guo; Jing Wen; Jin Yang; Yunzhuo Ke; Mangmang Wang; Mingming Liu; Feng Ran; Yunwen Wu; Pengfeng Li; Jiana Li; Hai Du (Planta, 2019)

Seasonal Dynamics of Gastrointestinal Nematode Infections of Goats and Emergence of Ivermectin Resistance in Haemonchus contortus in Hubei Province, China - Wei Yuan; Ke Lu; Hao Li; Jinming Liu; Chuanchuan He; Jintao Feng; Xin Zhang; Yudan Mao; Yang Hong; Yu Zhou; Jun Lu; Yamei Jin; et al. (Acta Parasitologica, 2019)

Asperpyrone F, a new dimeric naphtho- γ -pyrone from the edible fungus Pleurotus ostreatus - Xu Cai; Yang Yu; Qian Li; Ben-Ke Chen; Yun Huang; Xian-Wei Zou; Jin-Tian Tang; Bi-Sheng Huang (Natural Product Research, 2019)

Comparison of Phytoplankton Communities Between Melt Ponds and Open Water in the Central Arctic Ocean - Tianzhen Zhang; Yanpei Zhuang; Haiyan Jin; Ke Li; Zhongqian Ji; Yangjie Li; Youcheng Bai (Journal of Ocean University of China, 2019)

Orange and red carotenoid proteins are involved in the adaptation of the terrestrial cyanobacterium Nostoc flagelliforme to desiccation - Yi-Wen Yang; Yan-Chao Yin; Zheng-Ke Li; Da Huang; Jin-Long Shang; Min Chen; Bao-Sheng Qiu (Photosynthesis Research, 2019)

Treatment with MQA, a Derivative of Caffeoylquinic Acid, Provides Neuroprotective Effects against Cerebral Ischemia Through Suppression of the p38 Pathway and Oxidative Stress in Rats - Long Chen; Dan-ni Liu; Yu Wang; Xue-ying Liu; Shuai Han; Ke Zhang; Guo-yu Li; Xing Tian; Hang-yu Wang; Jin-hui Wang (Journal of Molecular Neuroscience, 2019)

Correction to: Analysis of the complete genomic sequence of a novel virus, areca palm necrotic spindle-spot virus, reveals the existence of a new genus in the family Potyviridae - Ke Yang; Minyuan Ran; Zengping Li; Meijiao Hu; Li Zheng; Wenbo Liu; Pengfei Jin; Weiguo Miao; Peng Zhou; Wentao Shen; Hongguang Cui (Archives of Virology, 2018)

Analysis of the complete genomic sequence of a novel virus, areca palm necrotic spindle-spot virus, reveals the existence of a new genus in the family Potyviridae - Ke Yang; Minyuan Ran; Zengping Li; Meijiao Hu; Li Zheng; Wenbo Liu; Pengfei Jin; Weiguo Miao; Peng Zhou; Wentao Shen; Hongguang Cui (Archives of Virology, 2018)

Electrochemical oxidation of Microcystis aeruginosa using a Ti/RuO2 anode: contributions of electrochemically generated chlorines and hydrogen peroxide - Li Lin; Xiaoyang Meng; Qingyun Li; Zhuo Huang; Linling Wang; Ke Lin; Jin Chen; John Crittenden (Environmental Science and Pollution Research, 2018)

Application of CRISPR/Cas9 technologies combined with iPSCs in the study and treatment of retinal degenerative diseases - Bincui Cai; Shuo Sun; Zhiqing Li; Xiaomin Zhang; Yifeng Ke; Jin Yang; Xiaorong Li (Human Genetics, 2018)

Analysis of the complete genome sequence of a potyvirus from passion fruit suggests its taxonomic classification as a member of a new species - Ke Yang; Haixia Yan; Li Song; Pengfei Jin; Weiguo Miao; Hongguang Cui (Archives of Virology, 2018)

3D FEM simulation of responses of LWD multi-mode resistivity imaging sonde - Zheng-Ming Kang; Shi-Zhen Ke; Xin Li; Jin-Tai Mi; Wei-Ning Ni; Ming-Yu Li (Applied Geophysics, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Agrobacterium tumefaciens-mediated transformation system for the important medicinal plant Dendrobium catenatum Lindl - Ji Chen; Li Wang; Jianbin Chen; Jin Huang; Fan Liu; Rong Guo; Li Yang; Aby Grabon; Ke Zhao; Fanlei Kong; Chen Liu; Mengliang Tian (In Vitro Cellular & Developmental Biology - Plant, 2018)

Tau-Induced Ca2+/Calmodulin-Dependent Protein Kinase-IV Activation Aggravates Nuclear Tau Hyperphosphorylation - Yu-Ping Wei; Jin-Wang Ye; Xiong Wang; Li-Ping Zhu; Qing-Hua Hu; Qun Wang; Dan Ke; Qing Tian; Jian-Zhi Wang (Neuroscience Bulletin, 2018)

Long-term Ameliorative Effects of the Antidepressant Fluoxetine Exposure on Cognitive Deficits in 3 × TgAD Mice - Li Jin; Li-Feng Gao; Dong-Sheng Sun; Hao Wu; Qun Wang; Dan Ke; Hao Lei; Jian-Zhi Wang; Gong-Ping Liu (Molecular Neurobiology, 2017)

Hyperechoic demarcation line between a tumor and the muscularis propria layer as a marker for deciding the endoscopic treatment of gastric submucosal tumor - Yu Zhang; Zhen Wang; Ting Jin; Kai-qiang Li; Ke Hao; Wei Zhang; Bao-ying Fei (Journal of Zhejiang University-SCIENCE B, 2017)

Mapping the effect of escitalopram treatment on amplitude of low-frequency fluctuations in patients with depression: a resting-state fMRI study - Li Wang; Xueni Li; Ke Li; Yunai Su; Yawei Zeng; Qinge Zhang; Gang Wang; Zhen Jin; Qingmei Kong; Tianmei Si (Metabolic Brain Disease, 2017)

Nitric Oxide Interacts with Caveolin-1 to Facilitate Autophagy-Lysosome-Mediated Claudin-5 Degradation in Oxygen-Glucose Deprivation-Treated Endothelial Cells - Jie Liu; John Weaver; Xinchun Jin; Yuan Zhang; Ji Xu; Ke J. Liu; Weiping Li; Wenlan Liu (Molecular Neurobiology, 2016)

Dihydromyricetin suppresses TNF-α-induced NF-κB activation and target gene expression - Nina Tang; Juan Ma; Ke Si Wang; Chunliu Mi; Ying Lv; Lian Xun Piao; Guang Hua Xu; Xuezheng Li; Jung Joon Lee; Xuejun Jin (Molecular and Cellular Biochemistry, 2016)

SIV Infection Impairs the Central Nervous System in Chinese Rhesus Macaques - Hang Liu; Qian-Hao Xiao; Jin-Biao Liu; Jie-Liang Li; Li Zhou; Qiao-Yang Xian; Yong Wang; Jing Zhang; Xu Wang; Wen-Zhe Ho; Ke Zhuang (Journal of Neuroimmune Pharmacology, 2016)

Association of interleukin-1 family cytokines single nucleotide polymorphisms with susceptibility to systemic sclerosis: an independent case–control study and a meta-analysis - Xiao-Lei Huang; Guo-Cui Wu; Yu-Jie Wang; Xiao-Ke Yang; Guo-Jun Yang; Jin-Hui Tao; Yu Duan; Jun-Wei Yan; Xiang-Pei Li; Dong-Qing Ye; Jing Wang (Immunologic Research, 2016)

Detection of novel adenoviruses in fecal specimens from rodents and shrews in southern China - Xue-yan Zheng; Min Qiu; Xue-mei Ke; Wei-jie Guan; Jin-ming Li; Shu-ting Huo; Shao-wei Chen; Xue-shan Zhong; Wen Zhou; Yi-quan Xiong; Jing Ge; Qing Chen (Virus Genes, 2016)

Transcriptomic analysis of the succulent xerophyte Zygophyllum xanthoxylum in response to salt treatment and osmotic stress - Qing Ma; Ai-Ke Bao; Wei-Wei Chai; Wen-Ying Wang; Jin-Lin Zhang; Yi-Xiao Li; Suo-Min Wang (Plant and Soil, 2016)

Large-scale comparative phosphoprotein analysis of maize seedling leaves during greening - De-Li Ning; Ke-Hui Liu; Chang-Cai Liu; Jin-Wen Liu; Chun-Rong Qian; Yang Yu; Yue-Feng Wang; Ying-Chun Wang; Bai-Chen Wang (Planta, 2016)

Histochemical analysis of testis specific gene 13 in human normal and malignant tissues - Hu Zhao; Xiaofeng Lai; Xinyuan Xu; Ke Sui; Xin Bu; Wenqiang Ma; Di Li; Kai Guo; Jinke Xu; Libo Yao; Wei Li; Jin Su (Cell and Tissue Research, 2015)

The inward-rectifying K+ channel SsAKT1 is a candidate involved in K+ uptake in the halophyte Suaeda salsa under saline condition - Hui-Rong Duan; Qing Ma; Jin-Lin Zhang; Jing Hu; Ai-Ke Bao; Li Wei; Qian Wang; Sheng Luan; Suo-Min Wang (Plant and Soil, 2015)

Laboratory investigation of the microbiologically influenced corrosion (MIC) resistance of a novel Cu-bearing 2205 duplex stainless steel in the presence of an aerobic marine Pseudomonas aeruginosa biofilm - Jin Xia; Chunguang Yang; Dake Xu; Da Sun; Li Nan; Ziqing Sun; Qi Li; Tingyue Gu; Ke Yang (Biofouling, 2015)

Spatial and temporal variations of snow cover in the Loess Plateau, China - Xin Jin; Chang‐Qing Ke; Yu‐Yue Xu; Xiu‐Cang Li (International Journal of Climatology, 2015)
Using 8‐day snow cover data of the Moderate Resolution Imaging Spectroradiometer from 2003 to 2013, we combined MOD10A2 and MYD10A2 to remove clouds and analysed the spatial and temporal variations of snow cover in the Loess Plateau, China. The snow cover throughout the entire Loess Plateau, including its central, southeast, and northwest sub‐regions, exhibits consistent seasonal trends. The majority of snow cover is present from early November to late March, including four sub‐cycles that involve separated snow cover accumulation and ablation processes. The maximum snow‐covered area occurs in January with an areal extent of 1 242 000 km 2 , whereas the minimum snow‐covered area is observed from May to August. There is an evident relationship between snow cover distribution and elevation. The majority of snow cover is located in the central sub‐region, whereas the lowest amount of snow cover exists in the northwest sub‐region. In the examined 11 years, the snow cover area and snow cover days fluctuated considerably without a significant trend. A significantly negative correlation between snow cover and intra‐annual temperature variation is observed. The monthly snow cover is found to correspond well with the Siberian High Central Intensity, particularly evident in November 2005, December 2007, December 2009, and December 2011. The response of the snow cover to the El Niño Southern Oscillation event was relatively weak, except for the significant cold event in late 2007 to early 2008 that caused a significantly positive snow cover anomaly.

Petrogenesis of diabase from accretionary prism in the southern Q iangtang terrane, central T ibet: Evidence from U – P b geochronology, petrochemistry and Sr – Nd – Hf – O isotope characteristics - Jin‐Xiang Li; Ke‐Zhang Qin; Guang‐Ming Li; Jun‐Xing Zhao; Ming‐Jian Cao (Island Arc, 2015)
The B angong– N ujiang suture ( BNS ) between the L hasa and Q iangtang terranes is an important boundary and its petrogenesis is controversial. Diabase from the accretionary prism in the southern Q iangtang terrane yields a zircon U – Pb age of 181.3 ± 1.4 Ma. All the diabases show tholeiitic basalt compositions, gentle enrichment patters of light rare earth elements ( REE ), variable enrichment in incompatible element concentrations (e.g. Th and Rb ), and no anomaly in high field strength elements (e.g. Nb and Ta ), similar to that of enriched mid‐ocean ridge basalt ( E ‐ MORB ). They have relatively homogeneous whole rock Nd (ε Nd (t) = 7.3–9.1) and zircon Hf – O isotopic compositions (ε Hf (t) = 14.8–16.1, and δ 18 O = 4.57–6.12‰), possibly indicating melting of the depleted mantle and no significant crustal contamination during the petrogenesis. The element variations suggest that the diabases were formed by plume–ridge interaction at a mid‐ocean ridge within the B angong– N ujiang ocean.

Evidence for Visually Mediated Copulation Frequency in the Scarab Beetle Anomala corpulenta - Jin Miao; Yu-Qing Wu; Ke-Bin Li; Yue-Li Jiang; Zhong-jun Gong; Yun Duan; Tong Li (Journal of Insect Behavior, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Isolation and genetic characterization of avian influenza virus H4N6 from ducks in China - Xiao-yuan Yuan; You-ling Wang; Ke-Xiang Yu; Yu-xia Zhang; Huai-ying Xu; Jin-xing Yang; Feng Li; Min-xun Song (Archives of Virology, 2015)

Water contents of Roberts Victor xenolithic eclogites: primary and metasomatic controls - Jin-Xiang Huang; Pei Li; William L. Griffin; Qun-Ke Xia; Yoann Gréau; Norman J. Pearson; Suzanne Y. O’Reilly (Contributions to Mineralogy and Petrology, 2014)

Long non-coding RNAs: new players in ocular neovascularization - Xue-Dong Xu; Ke-Ran Li; Xiu-Miao Li; Jin Yao; Jiang Qin; Biao Yan (Molecular Biology Reports, 2014)

Characterization of OsDREB6 responsive to osmotic and cold stresses in rice - Ya-Guang Ke; Zhi-Jun Yang; Shun-Wu Yu; Tian-Fei Li; Jin-Hong Wu; Huan Gao; Ya-Ping Fu; Li-Jun Luo (Journal of Plant Biology, 2014)

Antidiatom activity of marine bacteria associated with sponges from San Juan Island, Washington - Cuili Jin; Xiaying Xin; Siyu Yu; Jingjing Qiu; Li Miao; Ke Feng; Xiaojian Zhou (World Journal of Microbiology and Biotechnology, 2014)

ZxSOS1 is essential for long-distance transport and spatial distribution of Na+ and K+ in the xerophyte Zygophyllum xanthoxylum - Qing Ma; Yi-Xiao Li; Hui-Jun Yuan; Jing Hu; Li Wei; Ai-Ke Bao; Jin-Lin Zhang; Suo-Min Wang (Plant and Soil, 2014)

The PpLTP1 Primary Allergen Gene is Highly Conserved in Peach and Has Small Variations in Other Prunus Species - Ying-tao Ma; Xiang Zhou; Zhong-shan Gao; Xiong-wei Li; Hui-juan Jia; Hong-xia Wu; Rang-jin Xie; Zhi-qiang Wang; Ming-liang Yu; Ke Cao; Shuang-jian Chen; Ying-hui Li; et al. (Plant Molecular Biology Reporter, 2013)

Wip1 Phosphatase Involved in Lipopolysaccharide-Induced Neuroinflammation - Xiang Tan; Jingjing Zhang; Wei Jin; Lei Li; Wei Xu; Heyi Zheng; Ying Rui; Kaifu Ke; Ranran Zhou; Maohong Cao; Yongjin Pan (Journal of Molecular Neuroscience, 2013)

Effects of Exogenous Zinc on Cell Cycle, Apoptosis and Viability of MDAMB231, HepG2 and 293 T Cells - Yan-hong Wang; Ke-jin Li; Li Mao; Xin Hu; Wen-jie Zhao; An Hu; Hong-zhen Lian; Wei-juan Zheng (Biological Trace Element Research, 2013)

Threats to China’s biological resources posed by expanding international trade - Yun Song; Zhu Zhao; Jin Xu; Ke Chen; Mingfu Li (Biodiversity and Conservation, 2013)

Adaptation of spherical multicellular magnetotactic prokaryotes to the geochemically variable habitat of an intertidal zone - Ke Zhou; Wen‐Yan Zhang; Hong‐Miao Pan; Jin‐Hua Li; Hai‐Dong Yue; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2013)
Summary A combination of microscopic, molecular and biogeochemical methods was used to study the structure, phylogenetics and vertical distribution of spherical multicellular magnetotactic prokaryotes ( MMPs ) of intertidal sediments in the Y ellow S ea. These MMPs were 5.5 μm in diameter and composed of approximately 15–30 cells. They synthesized bullet‐shaped magnetites in chains or clusters. Phylogenetic analysis of 16 S rRNA gene sequences suggested that these MMPs represent a novel species affiliated to the D eltaproteobacteria. To study their vertical distribution and the relationship to geochemical parameters, sediment cores were collected after the redox potential was measured in situ . The sediments were composed of yellow, grey and black layers from the surface to depth. The spherical MMPs were concentrated near the grey‐black layer transition at a depth of 8–12 cm, while coccoid‐shaped magnetotactic bacteria near the yellow‐grey layer transition at a depth of 3–5 cm. The intertidal MMPs showed a deeper distribution at more reduced environments than coccoid‐shaped magnetotactic bacteria, and MMPs in lagoon sediments. Additionally the MMPs were concentrated significantly in layers with high proportion of fine sand and total organic carbon, rich in leachable iron but poor in nitrate. These results show an adaptation of spherical MMPs to the peculiar intertidal sediment habitat.

Molecular cloning and functional analysis of a blue light receptor gene MdCRY2 from apple (Malus domestica) - Yuan-Yuan Li; Ke Mao; Cheng Zhao; Xian-Yan Zhao; Rui-Fen Zhang; Hua-Lei Zhang; Huai-Rui Shu; Yu-Jin Hao (Plant Cell Reports, 2013)

Correlation between serum CA724 and gastric cancer: multiple analyses based on Chinese population - Xin-Zu Chen; Wei-Ke Zhang; Kun Yang; Lan-Lan Wang; Jin Liu; Li Wang; Jian-Kun Hu; Bo Zhang; Zhi-Xin Chen; Jia-Ping Chen; Zong-Guang Zhou; Xian-Ming Mo (Molecular Biology Reports, 2012)

The Group III Two-Component Histidine Kinase AlHK1 is Involved in Fungicides Resistance, Osmosensitivity, Spore Production and Impacts Negatively Pathogenicity in Alternaria longipes - Yi Yong Luo; Jin Kui Yang; Ming Liang Zhu; Chen Jian Liu; Hai Yan Li; Ze Bao Lu; Wen Zheng Pan; Zhong Hua Zhang; Wei Bi; Ke Qin Zhang (Current Microbiology, 2012)

Microsporogenesis, microgametogenesis, and pollen morphology of Ambrosia artemisiifolia L. in China - Jia-Xi Liu; Min Wang; Bing-Xiao Chen; Ping Jin; Jing-Yu Li; Ke Zeng (Plant Systematics and Evolution, 2012)

A novel β-glucosidase with lipolytic activity from a soil metagenome - Cheng-Jian Jiang; Gao Chen; Jie Huang; Qin Huang; Ke Jin; Pei-Hong Shen; Jun-Fang Li; Bo Wu (Folia Microbiologica, 2011)

Genetic differentiation and phylogeographical structure of the Brachionus calyciflorus complex in eastern China - XIAN‐LING XIANG; YI‐LONG XI; XIN‐LI WEN; GEN ZHANG; JIN‐XIA WANG; KE HU (Molecular Ecology, 2011)
Spatio‐temporal patterns and processes of genetic differentiation in passively dispersing zooplankton are drawing much attention from both ecologists and evolutionary biologists. Two opposite phylogeographical scenarios have already been demonstrated in rotifers, which consist of high levels of genetic differentiation among populations even on small geographical scales on the one hand and the traditionally known cosmopolitanism that is associated with high levels of gene flow and long‐distance dispersal via diapausing stages on the other hand. Here, we analysed the population genetic structure and the phylogeography of the Brachionus calyciflorus species complex in eastern China. By screening a total of 318 individuals from ten locations along a 2320‐km gradient and analysing samples from two growing seasons, we aimed at focusing on both small‐ and large‐scale patterns. We identified eight cryptic species and verified species status of two of these by sexual reproduction tests. Samples in summer and winter yielded different cryptic species. The distribution patterns of these genetically distinct cryptic species were diverse across eastern China, from full cosmopolitanism to local endemism. The two most abundant cryptic species BcWIII and BcSW showed a pattern of strong genetic differentiation among populations and no significant isolation by distance. Long‐distance colonization, secondary contact and recent range expansion are probably responsible for the indistinct pattern of isolation by distance. Our results suggest that geographical distance is more important than temporal segregation across seasons in explaining population differentiation and the occurrence of cryptic species. We explain the current phylogeographical structure in the B. calyciflorus species complex by a combination of recent population expansion, restricted gene flow, priority effects and long‐distance colonization.

A large outbreak of hand, foot, and mouth disease caused by EV71 and CAV16 in Guangdong, China, 2009 - Wu De; Ke Changwen; Li Wei; Corina Monagin; Yan Jin; Ma Cong; Zen Hanri; Su Jun (Archives of Virology, 2011)

The Pathway and Regulation of Salicylic Acid Biosynthesis in Probenazole-Treated Arabidopsis - Jin Yu; Jiong Gao; Xiao Yan Wang; Qiang Wei; Li Feng Yang; Kai Qiu; Ben Ke Kuai (Journal of Plant Biology, 2010)

Ophiocerol, a novel macrocylic neolignan from the aquatic fungus Ophioceras dolichostomum YMF1.00988 - Jin-Yan Dong†; Le Wang†; Hong-Chuang Song; Li-Mei Wang; Kai-Ze Shen; Rong Sun; Guo-Hong Li; Lei Li; Ke-Qin Zhang (Natural Product Research, 2010)

Field studies of the effectiveness of dynamic compaction in coastal reclamation areas - Shi-Jin Feng; Wei-Hou Shui; Li-Ya Gao; Li-Jun He; Ke Tan (Bulletin of Engineering Geology and the Environment, 2010)

The effect of root exudates from two transgenic insect-resistant cotton lines on the growth of Fusarium oxysporum - Xiao-gang Li; Biao Liu; Sondre Heia; Dou-dou Liu; Zheng-min Han; Ke-xin Zhou; Jin-jie Cui; Jun-yu Luo; Yang-ping Zheng (Transgenic Research, 2009)

Isolation and characterization of 13 microsatellite loci in the plateau pika (Ochotona curzoniae) - Ke-xin Li; Jia-ning Geng; Jin Yang; Yan-ming Zhang; Song-nian Hu (Conservation Genetics, 2009)

Distribution, sources, and potential risk of polycyclic aromatic hydrocarbons (PAHs) in drinking water resources from Henan Province in middle of China - Ying-ge Ma; Jin-ping Cheng; Fei Jiao; Ke-xin Duo; Zheng Rong; Ming Li; Wen-hua Wang (Environmental Monitoring and Assessment, 2008)

The distribution of HBV genotypes and clinical significance in familial clustering in an infected population with unfavorable prognosis - Jinfeng Liu; Yongqin Li; Tianyan Chen; Yuan Yang; Ke Wang; Yingli He; Qian Yang; Feng Ye; Yan Jin; Ting Qiu; Shumei Lin; Min Liu; et al. (Archives of Virology, 2008)

A mutant α-amylase with only part of the catalytic domain and its structural implication - T. Ke; X. D. Ma; P. H. Mao; X. Jin; S. J. Chen; Y. Li; L. X. Ma; G. Y. He (Biotechnology Letters, 2006)

Cloning and Characterization of OsORC2, A New Member of Rice Origin Recognition Complex - Ke-Gui Li; Jin-Shui Yang; Kotb Attia; Wei Su; Guang-Ming He; Xiao-Yin Qian (Biotechnology Letters, 2005)

Vernalization-induced flowering in wheat is mediated by a lectin-like gene VER2 - Wei-dong Yong; Yun-yuan Xu; Wen-zhong Xu; Xin Wang; Ning Li; Jin-song Wu; Tie-bing Liang; Kang Chong; Zhi-hong Xu; Ke-hui Tan; Zhi-qing Zhu (Planta, 2003)

Topaz–albite granites and rare-metal mineralization in the Limu District, Guangxi Province, southeast China - Jin-Chu Zhu; Ren-Ke Li; Fu-Chun Li; Xiao-Lin Xiong; Feng-Ying Zhou; Xiao-Long Huang (Mineralium Deposita, 2001)

Multiple origins of Tibetan Y chromosomes - Yaping Qian; Binzhi Qian; Bing Su; Jiankun Yu; Yuehai Ke; Zhengtao Chu; Lei Shi; Daru Lu; Jiayou Chu; Li Jin (Human Genetics, 2000)